Protective Effects of Selenium and Zinc Against Nickel Chloride-Induced Hormonal Changes and Oxidative Damage in Thyroid of Pregnant Rats - Imane Salah; Ounassa Adjroud; Awatef Elwej (Biological Trace Element Research, 2022)
Nickel chloride (NiCl2) is a heavy metal that may affect the function of the thyroid. Selenium (Se) and zinc (Zn) are essential trace elements involved in thyroid hormone metabolism. However, little is reported about thyrotoxicity during gestation. The current study aimed to investigate the protective effects of selenium and zinc against NiCl2-induced thyrotoxicity in pregnant Wistar rats. Female rats were treated subcutaneously (s.c.) on the 3rd day of pregnancy, with NaCl 0.9% and served as control, NiCl2 (100 mg/kg body weight (BW)) alone, or in association with Se (0.3 mg/kg, s.c.), ZnCl2 (20 mg/kg, s.c.), or both of them simultaneously. Oxidative stress parameters, thyroid biomarkers, and histopathological examination were evaluated. Results showed that NiCl2 exposure caused a significant decrease in maternal body weight and an increase in absolute and relative thyroid weight compared to the controls. NiCl2 administration also led to decreased plasma triiodothyronine (T3) and thyroxine (T4) with a concomitant significant increase in thyroid-stimulating hormone (TSH) levels when compared to that of control. In addition, an overall pro-oxidant effect was associated with a decrease in the reduced glutathione (GSH) and nonprotein thiol (NPSH) contents and the enzymatic activity of glutathione peroxidase (GPx) and superoxide dismutase (SOD), and an increase in malondialdehyde (MDA). These biochemical disturbances were confirmed by histological changes. However, the co-treatment of Se and/or ZnCl2 attenuates NiCl2-induced changes. Our findings suggested that Se and ZnCl2 ameliorated NiCl2-induced thyrotoxicity in pregnant Wistar rats by exhibiting antioxidant effects.

Nephroprotective Efficacy of Selenium and Zinc Against Potassium Dichromate-Induced Renal Toxicity in Pregnant Wistar Albino Rats - Anfal Fedala; Ounassa Adjroud; Omar Bennoune; Salwa Abid-Essefi; Foughalia, Abdelhamid; Rim Timoumi (Biological Trace Element Research, 2022)
Hexavalent chromium (CrVI) compounds are potent toxicants commonly used in numerous industries. Thus, potential toxic effects and health hazards are of high relevance. Selenium (Se) and zinc (Zn) are known for their antioxidant and chemoprotective properties. However, little is known about their protective effects against CrVI-induced renal damage during pregnancy. In this context, the present study aimed to investigate the protective efficacy of these two essential elements against potassium dichromate-induced nephrotoxicity in pregnant Wistar Albino rats. Female rats were divided into control and four treated groups of six each receiving subcutaneously on the 3rd day of pregnancy, K2Cr2O7 (10 mg/kg, s.c. single dose) alone, or in association with Se (0.3 mg/kg, s.c. single dose), ZnCl2 (20 mg/kg, s.c. single dose) or both of them simultaneously. The nephrotoxic effects were monitored by the evaluation of plasma renal parameters, oxidative stress biomarkers, DNA damage, and renal Cr content. The obtained results showed that K2Cr2O7 disturbed renal biochemical markers, induced oxidative stress and DNA fragmentation in kidney tissues, and altered renal histoarchitecture. The co-administration of Se and/or ZnCl2 has exhibited pronounced chelative, antioxidant, and genoprotective effects against K2Cr2O7-induced renal damage and attenuated partially the histopathological alterations. These results suggest that Se and Zn can be used as efficient nephroprotective agents against K2Cr2O7-induced toxicity in pregnant Wistar Albino rats.

The Mitigative Effect Of Selenium Against Hexavalent Chromium Induced- Toxicity In Liver Of Pregnant Wistar Rats - Anfal Fedala; Ounassa Adjroud; Salwa Abid-Essefi; Rim Timoumi (1st International Seminar on Pollution, Health, Environment and Bio-monitoring SIPSEB’21 DECEMBER 27-28, 2021)

L’évaluation de la perturbation thyroïdienne induite par le dichromate de potassium chez la rate gestante ALBINOS WISTAR - Anfal Fedala; Ounassa Adjroud (1er Séminaire International PERTURBATEURS ENDOCRINIENS ENVIRONNEMENT & REPRODUCTION (PEER 2021) tenu du 07 au 08 juillet, 2021)

CHROMIUM TOXICITY ON THE ELECTROLYTE BALANCE AND ADRENAL HISTOLOGY IN WISTAR MALE RATS - Sengouga, Djouhaina; Ounassa Adjroud; Imane Salah; Anfal Fedala (Nutr.Santé, 2021)

Protection of Steel Against Corrosion in Acid Medium Using Dihydropyrimidinone Derivatives: Experimental and DFT Study - Mammeri, Samia; Chafai, Nadjib; Hassina Harkat; Rachida, Kerkour; Chafaa, Salah (Iranian Journal of Science and Technology, Transactions A: Science, 2021)
Two dihydropyrimidinone derivatives (DHPM) were synthesized via the multi-component reaction, the yield of the synthesis reached 90%, and their structures were proved by IR, 1H and 13C NMR spectroscopy. The identified molecules were used for studying the corrosion inhibition of XC48 carbon steel in 0.5 mol L−1 H2SO4 solution. The inhibitory potentials of these compounds were determined by electrochemical methods exploiting the potentiodynamic polarization curves (Tafel method) and electrochemical impedance spectroscopy. Surface phenomena have been illustrated by atomic force microscopy. The results obtained show that the synthesized molecules are effective inhibitors, whose efficiency corrosion inhibition depends on the architecture of their structure, and it is proportional to the concentrations; it exceeds 94% for one of these inhibitors. The adsorption of these compounds on the metal surface approached the Langmuir’s adsorption isotherm. Furthermore, the electronic properties obtained using density function theory are in a good consensus with the experimental efficiencies of inhibition. The molecular dynamics simulations have allowed also simulating the interactions between the inhibitors and the metallic surface.

Chemical composition, in vitro antioxidant and antibacterial activities of Centaurea resupinata subsp. dufourii (dostál) greuter - Bouzghaia, Badra; Ben Moussa, Mohammed; Goudjil, Rima; Hassina Harkat; Patrick Pale (Natural Product Research, 2021)
The current study focuses on the chemical composition, and evaluation of antioxidant and antibacterial activity of the aerial parts of Centaurea resupinata subsp. dufourii. Using different chromatographic methods nine compounds 1–9 were isolated. The structural identification of isolated compounds was achieved using several spectroscopic methods NMR techniques (1H NMR, 13C NMR, COSY, HSQC, HMBC) and mass spectroscopy (ESI-MS) and by comparison with literature data. The structures of these compounds were identified as nicotiflorin (1), apigetrin (2), chrysoeriol (3), apigenin (4), chrysin (5), daucosterol (6), β-sitosterol (7), taraxastrerol (8) and lupeol (9). The antibacterial and antioxidant activities of ethyl acetate and n-butanol extracts have been evaluated. The antioxidant activity was assessed in vitro using DPPH radical scavenging method, which showed that ethyl acetate extract possessed an interesting antioxidant potential (IC50 = 36.263 ± 0.005 μg/mL).   <img alt="Graphical abstract" height="201" id="UF0001image" src="https://www.tandfonline.com/na101/home/literatum/publisher/tandf/journals/content/gnpl20/2021/gnpl20.v035.i22/14786419.2020.1715397/20211119/images/medium/gnpl_a_1715397_uf0001_c.jpg" width="500">

ZINC ALLEVIATES POTASSIUM DICHROMATE-INDUCED HEPATOTOXICITY IN PREGNANT WISTAR RATS - Anfal Fedala; ADJROUD OUNASSA; Asma Saouli; Salah Imane (Malaysian Journal Of Biochemistry & Molecular Biology, 2021)
The present study aimed to investigate the potential protective effects of zinc (Zn) against hexavalent chromium-induced hepatotoxicity in pregnant Wistar rats. Female rats were treated subcutaneously (s.c) on the 3 rd day of pregnancy, with NaCl 0.9 % and served as control, K₂Cr₂O7 (10 mg/kg bw) alone, or K₂Cr₂O7 in association with ZnCl2 (20 mg/kg bw). Hepatic biochemical parameters, oxidative stress biomarkers and DNA damage were monitored. Results revealed that K₂Cr₂O7 disturbed plasma ALT, AST, ALP and GGT, induced hepatic oxidative stress and DNA fragmentation. The co-treatment with Zn has alleviated K2Cr2O7-induced hepatotoxicity by exhibiting antioxidant and genoprotective effects in pregnant Wistar rats.

Protective effects of selenium and zinc against potassium dichromate–induced thyroid disruption, oxidative stress, and DNA damage in pregnant Wistar rats - Anfal Fedala; Ounassa Adjroud; Salwa Abid-Essefi; Rim Timoumi (Environmental Science and Pollution Research, 2021)
Hexavalent chromium (CrVI) is an environmental pollutant and an endocrine-disrupting metal. Se and Zn are essential trace elements, known to play a crucial role in thyroid homeostasis. However, there is a lack of data reporting thyrotoxicity during gestation. In this study, we investigated the protective effects of selenium and zinc against potassium dichromate–induced thyrotoxicity in pregnant Wistar rats. Thirty pregnant Wistar rats were divided into control and four treated groups receiving subcutaneously (s.c) on the 3rd day of pregnancy, K2Cr2O7 (10 mg/kg, s.c) alone, or in association with Se (0.3 mg/kg, s.c), ZnCl2 (20 mg/kg, s.c), or both of them simultaneously. The hormonal profile, oxidative stress biomarkers, DNA damage, and histological modifications were evaluated. Our main findings showed that K2Cr2O7 promoted hypothyroidism, oxidative stress, genotoxicity, and histological alterations in the thyroid gland. The co-treatment with Se or ZnCl2 has mitigated K2Cr2O7-induced thyrotoxicity in pregnant Wistar rats by exhibiting antioxidant and genoprotective effects. However, the combined co-treatment of both of them was less thyroprotective, and therefore, further investigations on the synergetic interaction of Se and Zn against CrVI toxicity using different doses and exposure routes are required.

Protective Effects of Selenium and Zinc Against Nickel Chloride–Induced Hormonal Changes and Oxidative Damage in Thyroid of Pregnant Rats - Imane Salah; Ounassa Adjroud; Awatef Elwej (Biological Trace Element Research, 2021)
Nickel chloride (NiCl2) is a heavy metal that may affect the function of the thyroid. Selenium (Se) and zinc (Zn) are essential trace elements involved in thyroid hormone metabolism. However, little is reported about thyrotoxicity during gestation. The current study aimed to investigate the protective effects of selenium and zinc against NiCl2-induced thyrotoxicity in pregnant Wistar rats. Female rats were treated subcutaneously (s.c.) on the 3rd day of pregnancy, with NaCl 0.9% and served as control, NiCl2 (100 mg/kg body weight (BW)) alone, or in association with Se (0.3 mg/kg, s.c.), ZnCl2 (20 mg/kg, s.c.), or both of them simultaneously. Oxidative stress parameters, thyroid biomarkers, and histopathological examination were evaluated. Results showed that NiCl2 exposure caused a significant decrease in maternal body weight and an increase in absolute and relative thyroid weight compared to the controls. NiCl2 administration also led to decreased plasma triiodothyronine (T3) and thyroxine (T4) with a concomitant significant increase in thyroid-stimulating hormone (TSH) levels when compared to that of control. In addition, an overall pro-oxidant effect was associated with a decrease in the reduced glutathione (GSH) and nonprotein thiol (NPSH) contents and the enzymatic activity of glutathione peroxidase (GPx) and superoxide dismutase (SOD), and an increase in malondialdehyde (MDA). These biochemical disturbances were confirmed by histological changes. However, the co-treatment of Se and/or ZnCl2 attenuates NiCl2-induced changes. Our findings suggested that Se and ZnCl2 ameliorated NiCl2-induced thyrotoxicity in pregnant Wistar rats by exhibiting antioxidant effects.

The antagonistic effect of the association of zinc and selenium on chromium induced toxicity in rat’s Testis - Sengouga, Djouhaina; Ounassa Adjroud; Anfal Fedala; Imane Salah (1ere Journée Scientifique sur la Biologie des plantes Médicinales 22 Janvier, 2020)

Hexavalent chromium - induced nephrotoxicity and its zinc and selenium antagonism in Wistar rat - Sengouga, Djouhaina; Ounassa Adjroud; Anfal Fedala; Imane Salah (Association nationale eco-conception, analyse de vie et développement durable affilié au réseau des clubs UNESCO en Algérie. Février, 2020)

Potential Protective Effects of Selenium and Zinc against Thyroid Toxicity Induced by Nickel in Preimplanted Wistar Albino Rats - Imane Salah; Ounassa Adjroud; Anfal Fedala; Asma Saouli (Toxicology International, 2020)
Nickel Is A Heavy Metal That May Affect The Function Of The Thyroid. The Present Study Was Undertaken To Assess The Protective Effects Of Selenium And Zinc Against Nickel-induced Thyrotoxicity In Preimplanted Wistar Albino Rats. Nickel Is Administered Alone (100 Mg/kg Body Weight) Subcutaneously Or In Combination With Selenium (0.3 Mg/kg Body Weight) Either With Zinc (20 Mg/kg Body Weight) Or Combined With Both Selenium And Zinc. All Groups Of Rats Were Injected On Day 3 Of Gestation In The Pre-implantation Period. Exposure Of Rats To Nickel Caused A Significant Decrease In Maternal Body Weight On Days 6 And 20 Of Gestation And An Increase In Absolute And Relative Thyroid Weight Compared To The Controls. Nickel Treatment Was Also Led In Decreased Plasma Triiodothyronine, Thyroxine With A Concomitant Significant Increase In Thyroid-stimulating Hormone Levels When Compared To Control. These Changes Were Confirmed By Histological Damages. However, Co-administration Of Selenium And/or Zinc To Nickel-treated Rats Restored The Hormonal And Histological Aspects. Our Findings Suggested That Selenium And Zinc Ameliorated Nickel Induced Thyroid Damage.

PROTECTIVE EFFECTS OF SELENIUM AND ZINC ON NICKEL CHLORIDE INDUCED REPRODUCTIVE TOXICITY IN WISTAR ALBINOS PREIMPLANTED RATS - Ismahene BOULILA; Ounassa Adjroud (Studia Universitatis Vasile Goldis Seria Stiintele Vietii (Life Sciences ), 2020)
: The aim of this study was to investigate that nickel chloride (NiCl2) induced reproductive toxicity in pre- implanted Wistar Rats and examined the possible protective effect of zinc chloride and selenium on plasma concentration of the hormones of 17 b etradiol (E2) and progesterone (prog); on the reproductive organ’s histology and on development. Experimental results showed the subcutaneous (s.c) administration of Nicl2 to Wistar albino Rats induced a decrease in plasma concentration of E2 and prog in addition, disturbance in development parameters and structural damages to the histology of the reproductive organs. Conversely, Se and ZnCl2 dues to the antioxidants property, regulate the secretion of E2 and Prog hormones, prevent alterations in the reproductive organs and in development in preimplanted rates receiving NiCl2.

Protective effect of zinc and selenium against chromium hematotoxicity and water consumption in the rats - Sengouga, Djouhaina; Ounassa Adjroud; Imane Salah; Anfal Fedala (1ere Journée de Biotoicologie et Bioactivité, 27 Nov, 2019)

Evaluation de l’hepatotoxicite induite par le dichromate de potassium chez les rates gestantes de la souche albinos wistar - FEDALA ANFAL; Ounassa Adjroud; Asma Saouli (2019)

Protective effect of zinc and selenium against chromium hematotoxicity and water consumption in the rats - Sengouga, Djouhaina; Ounassa Adjroud; Imane Salah; Anfal Fedala (1ere Journée de Biotoicologie et Bioactivité, 27 nov, 2019)

Phytochemical compounds and anti-corrosion activity of Veronica rosea - Rachid Ouache; Hassina Harkat; Patrick Pale; Oulmi, Kafia (Natural Product Research, 2019)
The aim of this work is the phytochemical study of the butanolic extract of the aerial parts of Veronica rosea. Four compounds 1–4 have been isolated using different chromatographic methods. The structures of these compounds were determined by NMR spectral analysis and mass spectroscopy. The adsorption and anticorrosion effects of this extract were investigated towards the corrosion of copper in 1 M HNO3 aqueous by the weight loss technique and potentiodynamic polarization. The results showed that the butanolic extract is a good inhibitor and the inhibition efficiency increases with increasing of concentration of the inhibitor. The adsorption of this extract on the copper specimen surface was spontaneous and obeyed the Langmuir’s adsorption isotherm. Large value of adsorption equilibrium Constant (K ads = 35 L g−1) was obtained. The polarization experiments confirmed the data obtained by gravimetric weight-loss. Tafel plot of polarization curves indicates that the extract acts as a mixed type inhibitor. <img alt="Graphical abstract" src="https://www.tandfonline.com/na101/home/literatum/publisher/tandf/journals/content/gnpl20/2019/gnpl20.v033.i09/14786419.2018.1474464/20190513/images/medium/gnpl_a_1474464_uf0001_oc.jpg">

Les complications chroniques chez les patients drépanocytaires - K Kala; F Soltani; M Saidi (Congrès maghrébin d'Hématologie , Octobre, 2019)

Lymphomes T cutanés primitifs : à propos de 4 cas. - N Bouabdallah; F Kacha; M Saidi (Congrès maghrébin d'Hématologie , Octobre, 2019)

Lymphome T anaplasique à grandes cellules ALK+ et ALK-- : étude descriptive et résultats thérapeutiques d’une série de 11 patients - A Bekache; M Aiche; M Saidi (Congrès maghrébin d'Hématologie , Octobre, 2019)

Aspects clinique et résultats thérapeutique de 08 cas de LNH T/NK - A Ghodbane; M Saidi (Congrès maghrébin d'Hématologie , Octobre, 2019)

LMC et survenue d' un second cancer à l'ère des ITK : à propos de 3 cas - F Soltani; F Kacha; M Aiche; M Saidi (Congrès maghrébin d'Hématologie , Octobre, 2019)

Résultats du traitement par Imatib* d'une série de 110 patients présentant une leucémie myéloïde chronique en phase chronique : étude mono centrique sur une période de 10 ans - F Soltani; F Kacha; M Saidi (Congrès maghrébin d'Hématologie , Octobre, 2019)

Description clinique, biologique et pronostique d'une série de 114 patients présentant une leucémie myéloïde chronique: étude mono centrique sur une période de 10 ans - F Soltani; F Kacha; M Saidi (Congrès maghrébin d'Hématologie , Octobre, 2019)

Description clinique, biologique et pronostique d'une série de 114 patients présentant une leucémie myéloïde chronique: étude mono centrique sur une période de 10 ans - F Soltani; F Kacha; M Saidi (Congrès maghrébin d'Hématologie , Octobre, 2019)

Leucémie Myéloide Chronique et survenue d'un second cancer à l'ère des ITK : à propos de 3 cas et revue de la littérature - F Soltani; M Aiche; F Kacha; M Saidi (Congrès maghrébin d'Hématologie , Octobre, 2019)

Etude de la diversité des insectes du cèdre de l'atlas dans le Parc National de Belezma (Batna - Algérie) - CHAFAA Smail ("Premier Colloque International sur la Lutte Biologique et Intégrée en Algérie", CILBIAl, 2019)

Biodiversité entomologique de l’Abricotier dans la région de T’Kout et Ouled Si Slimane (Wilaya de Batna) - CHAFAA Smail (VIIème congrès international de Biotechnologie et Valorisation des Bio-Ressources, 2019)

ETUDE BIOECOLOGIQUE DU PSYLLE DE L’OLIVIER EUPHYLLURA OLIVINA COSTA 1839 (HEMIPTERA : PSYLLIDAE) DANS LA REGION D’EL-DJALFA - CHAFAA Smail ("Premier Colloque International sur la Lutte Biologique et Intégrée en Algérie", CILBIAl, 2019)

BIO-ECOLOGIE DE LA MINEUSE DE LA TOMATE TUTA ABSOLUTA (LEPIDOPTERA : GELECHIIDAE) ET L’EVALUATION DE SES DEGATS SUR LA CULTURE DE LA TOMATE EN PLEIN CHAMP DANS LA REGION DE BATNA - CHAFAA Smail ("Premier Colloque International sur la Lutte Biologique et Intégrée en Algérie", CILBIAl, 2019)

ESTIMATION DES DEGATS OCCASIONNES PAR SITOPHILUS ORYZAE L. (COLEOPTERA : CURCUUONIDAE)SUR LES POIS STOCKES DANS LA WILAYA DE BATNA (EST ALGERIE) - CHAFAA Smail ("Premier Colloque International sur la Lutte Biologique et Intégrée en Algérie", CILBIAl, 2019)

Synthèse et caractérisation des hétérocycles oxygénés de type benzoxanthenes a visée thérapeutique - Zouchoune Soria (Séminaire National de Biodiversité, Biologie Médicale et Ecologie Environnementale 30-31 Octobre, 2019)

Evaluation phytochimique et antimicrobienne de la plante cytus purgans - BOUZGHAIA Badra (Séminaire National de Biodiversité, Biologie Médicale et Ecologie Environnementale 30-31 Octobre, 2019)

Etude des metabolites secondaires de la plante Cytisus purgans - BOUZGHAIA Badra (Troisième colloque Maghrébin sur la Chimie Hétérocyclique CMCH3-2019- Palais des Sciences de Monastir MESRS 28-29 juin, 2019)

Phytochimical analysis from the plant centaurea tenuifolia - BOUZGHAIA Badra (The second international symposium Medicinal Plants and Materials (MPM-2019), February 15 to 17, 2019)

Effet pretecteur de la supplementation en sélénium contre la néphrotoxicité induite par le chlorure de nickel chez la rate gestante - Imane Salah; Ounassa Adjroud (Deuxième Journée Aurassienne de Biologie Moléculaire, 2019)

Hematotoxicite induite par le nickel chez la rate gestante de souche wistar - Ismahene BOULILA; Ounassa Adjroud (Premier Colloque International sur la Lutte Biologique et Intégrée en Algerie « CILBIA1 » . Du 04-06 février, 2019)

Etude de la toxicité rénale du chlorure de nickel chez la rate gestante Albinos Wistar - Imane Salah; Ounassa Adjroud (Premier Colloque International sur la Lutte Biologique et Intégrée en Algerie « CILBIA1 » . Du 04-06 février, 2019)

Evaluation de l’hepatotoxicite induite par le dichromate de potassium chez les rates gestantes de la souche albinos wistar - FEDALA ANFAL (Premier Colloque International sur la Lutte Biologique et Intégrée en Algerie « CILBIA1 » . Du 04-06 février, 2019)

Effets du dichromate de patassium sur la ligne lymphocytaire et leucocytaire chez la rate gestante Albinos Wistar - Asma Saouli; Ounassa Adjroud; Asma Saouli (Premier Colloque International sur la Lutte Biologique et Intégrée en Algerie « CILBIA1 » . Du 04-06 février, 2019)

Neutropenie Chimio–induite : Profil Bactériologique. - A Kassah Laouer; Amina Messala; Mahdia Saidi (Journal Algérien de Médecine, 2019)

Entomofauna investigations in the apricot orchards,Prunus armeniaca L. (Rosales Rosaceae), in Ouled Si Slimane, Batna, North EastAlgeria - Smail Chafaa; Sabrina Belkhadria; Fateh Mimeche (Biodiversity Journal, 2019)
Researches carried out in the past years allowed to list an entomofauna that lives on the apricot orchards, Prunus armeniaca L. (Rosales Rosaceae), in Ouled Si Slimane (Batna Department, Algeria). The investigated period was from October 2014 until May 2015. The sampling techniques used were: hunting in sight, barber pots, colorful traps, entomological umbrella and the filleting net. We have identified a total of 125 species divided into 9 orders and 54 families in which Coleoptera and Hymenoptera were quantitatively represented. The phytophagous were the most present. Its Shannon Value exceeds 4.5 Bits and indicates a Specific Richness of the insects and diversification of ecological niches in this kind of fauna.

Diversity of insects associated with olive (Oleaceae) groves across a dryland climate gradient in Algeria - Smail Chafaa; Fateh Mimeche; Haroun Chenchouni (The Canadian Entomologist, 2019)
This study investigated insect diversity of olive (Olea europaea Linnaeus (Oleaceae)) groves grown in arid and semiarid climates in northeastern Algeria. Using several sampling techniques, a total of 1326 insect specimens were collected and identified into 151 species, 124 genera, 65 families, and 10 orders. Hymenoptera and Coleoptera were quantitatively the most abundant, whereas the dominant functional feeding groups were phytophages then predators. The entomofauna included several olive pests such as Bactrocera oleae (Rossi) (Diptera: Tephritidae), Parlatoria oleae (Colvée) (Hemiptera: Diaspididae), Euphyllura olivina (Costa) (Hemiptera: Liviidae), and Liothrips oleae Costa (Thysanoptera: Phlaeothripidae). Although insect diversity parameters recorded for both observed and expected species richness were higher in olive groves grown under semiarid compared with arid climate, the completeness rate of species richness obtained using the nonparametric incidence estimators was higher in arid olive groves. Generalised linear models showed that the number of individuals and species richness varied significantly between climates (P < 0.01), whereas the variation of the rest of diversity parameters was not significant. Diversity traits of insect assemblage of each climatic region were positively correlated. Besides, the Mantel permutation test revealed similar patterns (r = 0.91, P < 0.0001) between correlation matrices of the two climates. When increasing the number of samples, species richness extrapolation revealed that diversity is expected to increase by 130% in olive groves grown under arid climate and 93% in semiarid climate. These increases are related to continuous appearance of rare and scarce insects as demonstrated by species rarefaction curves. Even with high evenness values of insect communities, similarity was low between climate indicating the rarity and scarcity of populations.

Phytochemical compounds and anti-corrosion activity of Veronica rosea - Rachid Ouache; Hassina Harkat; Patrick Pale; Oulmi, Kafia (Natural Product Research, 2019)
The aim of this work is the phytochemical study of the butanolic extract of the aerial parts of Veronica rosea. Four compounds 1–4 have been isolated using different chromatographic methods. The structures of these compounds were determined by NMR spectral analysis and mass spectroscopy. The adsorption and anticorrosion effects of this extract were investigated towards the corrosion of copper in 1 M HNO3 aqueous by the weight loss technique and potentiodynamic polarization. The results showed that the butanolic extract is a good inhibitor and the inhibition efficiency increases with increasing of concentration of the inhibitor. The adsorption of this extract on the copper specimen surface was spontaneous and obeyed the Langmuir’s adsorption isotherm. Large value of adsorption equilibrium Constant (K ads = 35 L g−1) was obtained. The polarization experiments confirmed the data obtained by gravimetric weight-loss. Tafel plot of polarization curves indicates that the extract acts as a mixed type inhibitor. <img alt="Graphical abstract" src="https://www.tandfonline.com/na101/home/literatum/publisher/tandf/journals/content/gnpl20/2019/gnpl20.v033.i09/14786419.2018.1474464/20190513/images/medium/gnpl_a_1474464_uf0001_oc.jpg">

ETUDE BIOECOLOGIQUE DU PSYLLE DE L’OLIVIER EUPHYLLURA OLIVINA COSTA 1839 (HEMIPTERA : PSYLLIDAE) ET LEURS ENNEMIS NATURELS DANS LES OLIVERAIES DE LA REGION D’EL-DJALFA - CHAFAA Smail (Troisième colloque national sur la Biodiversité en Algérie CNBA3, 2018)

ETUDE DES INSECTES DE LA FEVE STOKEE DANS DES LOCALITES COMMERCIALES A BATNA (EST ALGERIE) - CHAFAA Smail (Troisième colloque national sur la Biodiversité en Algérie CNBA3, 2018)

Étude des pertes causées par Bruchus rufimanus sur la fève stockée dans la wilaya de Batna (Est Algérie) - CHAFAA Smail (Premier Séminaire international sur L'Agroalimentaire « SI A 2018 », 2018)

COMPOSITION CHIMIQUE ET ACIVITE ANTI OXYDANTE DES PARTIES AÉRIENNES DE VERONCA ROSEA - OUACHE Rachid (9eme Congres National de la SAC, 8-10 Mai , USTHB Bab Ezzeouar, 2018)

SYNTHESE ET CARACTERISATION DES HETEROCYCLES AZOTES DE TYPE 1,4-DIHYDROPYRIDINES A VISEE THERAPEUTIQUE - Zouchoune Soria (Séminaire National de Biologie, Environnement et Santé (SNBES)-Université du 20 aout 1955 - du 08 au 09 Octobre, 2018)

Etude phytochimique et évaluation biologique de La plante Centaurea Tenuifolia - BOUZGHAIA Badra (Séminaire National de Biologie, Environnement et Santé (SNBES)-Université du 20 Aout 1955 -du 08 au 09 Octobre, 2018)

Influence du traitement de recuit sur la microstructure et les propriétés mécaniques et électriques d'un fil de cuivre tréfilé industriellement - BAIRA Fayçal (4Th International Conference on Energy, Materials, Applied Energetics and pollution (ICEMAER'18), 29th and 30th April, 2018)

Etude de la texture et les propriétés mécaniques et électriques des fils de cuivre tréfilés et recuits - BAIRA Fayçal (5Th International Conference on Green Energy, and Environmental Engineering (GEEE-2018),28th and 30th April, 2018)

Multi-scale analysis by EBSD, X-ray diffraction and neutron diffraction of microstructure and texture of Al-Mg-Si aluminum alloy wires drawn and annealed; 27th Int. - BAIRA Fayçal (Metallurgical & Material Conf .(METAL 2018), May 23-25, 2018)

Effect of deformation on the structural and mechanical properties of drawn copper wires - BAIRA Fayçal (International Conference on Materials Science (ICMS2018), SETIF1University, Algeria ,September 12-14, 2018)

Study and characterization of the microstructure, crystallographic texture and mechanical properties of AGS aluminum alloy cold drawn wire - BAIRA Fayçal (International Conference on Materials Science (ICMS2018), SETIF1University, Algeria ,September 12-14, 2018)

POLYPHENOLIC CONSTITUENTS FROM AERIAL PART OF VERONCA ROSEA - Zouchoune Soria (Séminaire International sur les plantes Médicinales(SIPM-2018)-Université d’el-oued du 17 au18 Janvier, 2018)

SYNTHESE DE BENZOXANTHENES CATALYSEE PAR COMPLEXE A21.CU(I) - Zouchoune Soria (5ème Colloque International de Chimie CIC-5, Batna, 4 -5 Décembre, 2018)

One-Pot Synthesis of Xanthene Derivatives Using A21.Cu(I) as Catalyst - Zouchoune Soria (4ème Journées Internationales de Chimie Organique de Annaba JICOA’18, Annaba, 1-3 Décembre, 2018)

Evaluation phytochimique de la plante cytisus purgans - BOUZGHAIA Badra (CINQUIEME COLOQUE INTERNATIONAL DE CHIMIE CIC-5, Université de Batna 4-6 Décembre, 2018)

ISOLATION AND STRUCTURAL ELUCIDATION OF BIOACTIVE COMPONDS FROM CENTAUREA - BOUZGHAIA Badra (Quatrième Journées Internationales de chime Organique de Annaba-JICOA’18, 1,2 et 3 Décembre, 2018)

CHEMICAL CONSTITUENTS FROM AERIAL PART OF CENTAUREA TENUIFOLIA - BOUZGHAIA Badra (Séminaire International sur les plantes Médicinales(SIPM-2018)-Université d’el-oued du 17 au18 janvier, 2018)

Les effets du chrome hexavalent sur la ligne thrombocytaire chez la rate gestante Albinos Wistar - Asma Saouli; Ounassa Adjroud; Anfal Fedala (Séminaire National Biologie Environnement et Santé « SNBES 2018 ». 08-09 Octobre, 2018)

Contribution a la recherche des effets du chrome hexavalent sur la leucopoïèse chez la rate gestante de la souche Albinos Wistar - SAOULI ASMA (Le séminaire national<<Biotechnologie,Environnement et Santé>>(BiEnSa’2018).28 et 29 Novembre November, 2018)

L’effet néphrotoxique du chrome hexavalent chez la rate gestante de la souche Albinos wistar - Anfal Fedala; Ounassa Adjroud; Asma Saouli (Le séminaire national<<Biotechnologie,Environnement et Santé>>(BiEnSa’2018).28 et 29 November, 2018)

Contribution à la recherche des effets immunotoxiques du chrome hexavalent chez la rate gestante de la souche Albinos Wistar. - Anfal Fedala; Ounassa Adjroud; Asma Saouli (Le Premier Séminaire International sur L’Agroalimentaire « SIA 2018 », 2018)

Epidemiological Study of Aplastic Anemia in Algeria for 844 Cases over 10 Years (2007-2016) - F Mehdid; N Rekkab; S Oukid; Abad, MT; M Bradai; Hamdi, S; F Boukhemia; Hamladji, RM; R Ahmed Nacer; M Allouda; H Ait-Ali; S Benaichou; et al. (Blood, 2018)
Introduction: The aim of this work is to establish an epidemiological approach of aplastic anemia (AA) in Algeria, to identify the different therapeutic strategy and the patients outcomes. Material and methods: This is a retrospective multi-center epidemiological study over 10 years (from 01 January 2007 to 31 December 2016). The source of information is represented by the medical files and the consultation sheets. The collection of information is ensured by the fact sheets established and distributed to the departments Hematology and Pediatrics at the national level. Results: A total of 844 cards were received, concerning 844 patients including 746 adults and 94 children. The overall incidence of the disease is 0.21, it varies from 0.16 to 0.28 / 100000 inhabitants / year depending on the year. The average age is 34.7 years with extremes ranging from 1 month to 91 years, the sex ratio (M / F) is 1 (420/424). In adults there is a slight male predominance: sex ratio is 1.11 (421/378). AA is acquired in 806 patients (95.4%) and congenital in 38 patients (4.6%). Among the acquired AA: idiopathic = 694 (86.1%), toxic = 18 (2.23%), viral: 17 (2.1%): HBV = 13, HCV = 3, HIV = 1, drug = 13 (1.6%), gestational = 9, (1.1%), hematopoietic tuberculosis = 1. The presence of an HPN clone in 55 out of 261 patients studied was 21%, associated with a dysimmunitary disease = 5. In congenital AM, Fanconi anemia = 35, Blackfand-Diamond = 2, congenital dyskeratosis = 1. The prognostic classification according to the Camitta criteria and the EBMT criterion: out of 540 evaluable records found: very severe = 83 (15.3%), severe = 291 (53.8%), moderate = 166 (30.7%). CsA-SAL reference immunosuppressive therapy was instituted in only 49 pts (13.1%) with severe and very severe forms. It resulted in a hematologic response in 18 patients (36.5%), 15 patients died and 16 patients were probably lost to follow-up. Three hundred and twenty-seven pts (38.7%) received allogeneic hematopoietic stem cell transplant at CPMC (n = 316) and EHU (n = 11); = 277), Fanconi anemia (n = 44), amgacaryocytosis in its aplastic form (n = 3), erythroblastopenia in aplastic form (n = 2), untagged constitutional medullary aplasia (n = 1). As of 31/12/2016: 344 pts are alive, 208 died, 194 lost sight of and 98 pts whose fate is not specified on the cards. Conclusion: AA is a rare , the incidence is 0.2 / 100000 inhabitants / year. It affects young adults with a slight male predominance in adults, idiopathic forms are in the foreground and severe forms predominat Disclosures No relevant conflicts of interest to declare.

Epidemiological Study on β-Thalassemia in Algeria - Fatiha Grifi; A Djenouni; S Bougherira; Abad, MT; C Boucherit; N Boudjerra; N Zidani; C Aboura; A Aribi; M Belhani; S Nekkal; H Bouaricha; et al. (Blood, 2018)
Introduction : Among genetic diseases in hematology, β Thalassemia ranks second after sickle cell disorders in Algeria. Given the seriousness and cost of the care that arises, a national action plan is needed. As a starting point, a national survey is essential to know the epidemiological situation of this disease. Objective : To determine the soci-demographic, diagnosis and evolution characteristics of major and intermediate thalassemia in Algeria. Materiels and Methods : This is a multicenter, retrospective, analytical study of 775 patients with thalassemia major (TM: 598 cases) and intermediate (TI: 177 cases). This national survey is representative of 21 services (Hematology: 19, Pediatrics: 03). The data was collected from medical records on a survey card distributed to all relevant services. Results : As of January 1, 2017, the prevalence of β Thalassemia estimated from this study is of the order of 3.47 cases per 100 000 inhabitants. The current average age of major thalassemia (MT) is 17.90 years, with extremes of [1-44 years], that of intermediate form (IT) is 23 years old with extremes of [1-61 years], the sex ratio is 1.15. The concept of consanguinity is specified in 499 patients and is present in 49.30% of cases, the geographical origin of patients is variable, 53% are from the center of the country and 43% from the east. The circumstances of the diagnosis are known in 87.25% of subjects, these are clinical symptoms in 93.91% of patients, with an average age at diagnosis of 16.31 months for MT and 5.5 years for IT. The diagnosis is neonatal in only 5.68% of cases. Blood cells transfusion needs are known in 80% of our cohort, 86% receive a systematic and regular diet; 554 patients are on chelation therapy, the main modality being deferoxamine or Deferasirox type monotherapy. 40 MT patients received Hematopoetic Stem Cell Transplantation. The monitoring of iron overload was based mainly on the determination of ferritinemia, only 8.8% of patients received cardiac and hepatic MRI. Various complications associated with iron overload have been reported, the most common being: Hepatic injury (48%), heart disease (36%), diabetes (30%), hypothyroidism (29.17). %), with average ages of onset of 26.67, 18, 19, and 14.50 years, respectively. In addition, viral serology was performed in 536 patients, 64 (11.9%) of whom were carriers of anti-HCV Ab. Conclusion : The quality and life expectancy of thalassemic patients has improved significantly in recent years; complications related to iron overload remain the leading cause of death, the means of evaluation remain insufficient in our country. In addition, the care of our patients must be standardized on the national territory. Disclosures No relevant conflicts of interest to declare.

DYNAMIQUE DES POPULATIONS ET MODALITES D’INFESTATION DE POLLINIA POLLINI COSTA, 1857 (HOMOPTERA, ASTEROLECANIIDAE) SUR L’OLIVIER OLEA EURPAEA L. DANS LA REGION SEMI-ARIDE D’ARRIS (BATNA, NORD-EST D’ALGERIE) - NAOUAL BOUKHTACHE; ABDELKRIM SI BACHIR; MOHAMED BELHAMRA; Smail Chafaa; CHERIF GHAZI; SAWSEN OUCHEN (Courrier du Savoir, 2018)
Le suivi démo-écologique de la cochenille Pollinia pollini est réalisée dans une oliveraie de la région semi-aride d’Arris (Nord-est Algérie) durant une période d’une année, allant de janvier à décembre 2015. L’étude du mode d’infestation de l’olivier Olea eurpaea par la cochenille est basée sur des dénombrements des différents stades de développement de l’espèce sur les rameaux. Ces dénombrements sont réalisés suivant les orientations de l’arbre (Nord, Est, Sud, Ouest et Centre) et suivant le mode d’installation de la cochenille sur les rameaux (à la surface des rameaux, aux aisselles des rameaux et des feuilles ou à l’intérieur du bois). Ce travail montre que P. pollini évolue en une seule génération annuelle. La parution des larves du premier stade commence à la troisième décade de mars et se poursuit jusqu’à la mi-août. Les larves du deuxième stade apparaissent à la troisième décade d’avril et enregistrent leur pic en juillet. Les femelles adultes, qui sont présentes le long de la période d’étude, enregistrent leurs effectifs maximaux en octobre et en novembre. L’étude de l’abondance globale de P. pollini en fonction des orientations montre que l’espèce s’installe préférentiellement dans les parties Nord, Est et Ouest de l’arbre, avec des proportions relativement proches allant de 20 % à 22 %. Le suivi de l’emplacement de P. pollini sur les rameaux de l’olivier montre que la cochenille s’installe dans trois emplacements différents. Elle préfère s’installer aux aisselles des rameaux et des feuilles (43,23 %), à la surface des rameaux (29,15 %) et à l’intérieur du bois (27,62 %).

Seasonal study of the diet of the barbel Luciobarbus callensis (Valencienne1842) in the K'sob reservoir (M'Sila, Algeria) - Fateh Mimeche; Abdelghani Zedam; Smail Chafaa; Hayet Mimeche; Mohamed Biche (Journal of Water Science, 2018)
The composition of the diet of the barbel (Luciobarbus callensis) was studied in the K'sob reservoir near the town of M'Sila (Algeria). The capture of the barbels was carried out between September 2010 and August 2011.The diet was studied from 379 specimens collected by trammel net. During the study period, it was noted that the food spectrum essentially consisted of Chironomids, Ephemeroptera and Copepods, which are abundant in the environment. The barbel of the K'sob reservoir has a seasonal food pattern influenced by climatic and ecological conditions and by its reproductive cycle. The diet of L. callensis in the study area is omnivorous, with a zoo-benthophage tendency.

Étude saisonnière du régime alimentaire du barbeau Luciobarbus callensis (Valencienne 1842) dans le réservoir de K'sob (M'Sila, Algérie) - Fateh Mimeche; Abdelghani Zedam; Smail Chafaa; Hayet Mimeche; Mohamed Biche (Revue des sciences de l’eau, 2018)
The composition of the diet of the barbel (Luciobarbus callensis) was studied in the K'sob reservoir near the town of M'Sila (Algeria). The capture of the barbels was carried out between September 2010 and August 2011.The diet was studied from 379 specimens collected by trammel net. During the study period, it was noted that the food spectrum essentially consisted of Chironomids, Ephemeroptera and Copepods, which are abundant in the environment. The barbel of the K'sob reservoir has a seasonal food pattern influenced by climatic and ecological conditions and by its reproductive cycle. The diet of L. callensis in the study area is omnivorous, with a zoo-benthophage tendency.

Effets de la forte dose de chlorure de nickel seul administrée par voie sous cutanée sur les paramètres hématologique et l’histologie des testicules chez les rats males de la soucheWistar - Boulila, Ismahan; Ounassa Adjroud (6ème journées de l’ATT : processus toxiques-bioactivité-biosurvaillance.21,23/01/2017, 2017)

L’effet du nickel administré par voie sous cutanée et son éventuelle interaction avec le sélénium et le zinc sur la leucopoïèse et l’histologie hépatique - Anfal Fedala; Ounassa Adjroud (6èmes Journées Scientifiques de l’Association Tunisienne de Toxicologie(ATT). 21 -23 Janvier, 2017)

Données du Registre Algérien du Myélome Multiple (RAMM) sur 2 années(juin 2014-juin 2016). - M Saidi; F Soltani (Congrès Maghrébin d'Hématologie, 2017)

DIFFERENTIATION SYNDROME IN ACUTE PROMYELOCYTIC LEUKEMIA: A MONO CENTRIC STUDY - SAIDI Mahdia (7th INTERNATIONAL SYMPOSIUM ON ACUTE PROMYELOCYTIC LEUKEMIA, 2017)

EPIDEMIOLOGY, DIAGNOSIS, CLINICAL FEATURES AND OUTCOME OF ACUTE PROMYELOCYTIC LEUKEMIA PATIENTS TREATED AT BATNA AGAINST CANCER CENTER IN ALGERIA - SAIDI Mahdia (7th INTERNATIONAL SYMPOSIUM ON ACUTE PROMYELOCYTIC LEUKEMIA, 2017)

DIVERSITE ENTOMOLOGIQUE DES ZONES HUMIDES DE LA REGION D’EL-KALA - CHAFAA Smail (Deuxième colloque national sur la Biodiversité en Algérie CNBA2, 2017)

Contribution à l’étude bioécologique des ennemis naturels du Psylle de l’Olivier (euphylura olivina Costa, 1839, Hemiptera : Psyllidae) dans une oliveraie de la région de Ain Touta-Batna –Algérie. - CHAFAA Smail (Séminaire International « Environnement, Agriculture et Biotechnologie » SIEAB, 2017)

PREMIERES DONNEES SUR LE CYCLE BIOLOGIQUE ET LA DYNAMIQUE DES POPULATIONS DU PSYLLE DE L’OLIVIER (EUPHYLLURA OLIVINA CSTA (1839) HEMIPTERA : PSYLLIDAE - CHAFAA Smail (AFPP – 11e CONFÉRENCE INTERNATIONALE SUR LES RAVAGEURS ET AUXILIAIRES EN AGRICULTURE MONTPELLIER, 2017)

Effets de l’administration par voie sous- cutanée du nickel associe avec le zinc et le sélénium sur les paramètres hématologique et rénaux chez les rat Wistar - Salah Imane; Ounassa Adjroud (Vème Congrès International de Biotechnologie et Valorisation des Bio Ressources.22-25 Mars, 2017)

Effet de chlorure de nickel sur l’érythropoïèse et les organes génitaux chez la rate gestante Wistar. Rôle du zinc et du sélénium - BOULILA ISMAHANE (les 6èmes journées scientifiques de l’association Tunisienne de toxicologie(ATT). 21 -23 janvier, 2017)

L’effet du nickel administré par voie sous cutanée et son éventuelle interaction avec le sélénium et le zinc sur la leucopoïèse et l’histologie hépatique - FEDALA ANFAL (les 6èmes journées scientifiques de l’association Tunisienne de toxicologie(ATT). 21 -23 janvier, 2017)

Effets de la forte dose de chlorure de nickel seul administrée par voie sous cutanée sur les paramètres hématologique et l’histologie des testicules chez les rats males de la soucheWistar - SAOULI ASMA (Vème congrès International de Biotechnologie et valorisation des Bioressources. 22-25 Mars, 2017)

Selenium Administration Can Alter Some Biochemical Parameters in Rats - Ounassa Adjroud (Conference on Healthcare & Life-Science Research (ICHLSR), 28-29 July 2017, 2017)

Epidemiological Data from the Algerian Multiple Myeloma Registry (AMMR) over 2 Years (June 2014-June 2016): Report of the Algerian Multiple Myeloma Study Group (GETMA) - Mahdia Saidi; Abad, MT; Taoussi, S; C Ghezlane; Hamladji, RM; R Ahmed-Nacer; F Belhadri; H Moussaoui; H Ait-Ali; H Aftisse; Fz Ardjoun; SE Belakehal; et al. (Blood, 2017)
Introduction: Multiple myeloma (MM) is the second hematological malignancy in Western countries with varying incidence across countries and ethnicities. In France, the incidence rate in 2012 is 4.2 in men and 2.0 in women, in USA it is 5.6 but in the population of African origin it is 11.1. In Maghreb, the incidence is 1,1 in Algeria and Morocco and 1.4 in Tunisia in 2004. Although epidemiological transition has taken place in our country, the results of epidemiological data on cancers in general and hematological malignancies in particular are remarkably different from those described in the Western literature. Aims : Two epidemiological approaches were carried out in Algeria, the first covering a period of 12 years (1995-2005) and the second of 2006-2012, the incidence of MM was the same of 1.1 and 1.01 respectively. These were retrospective studies with the limitations of this type of study, hence the need to create a register that would collect the data in a prospective and real-time manner. This register, known as AMMR (Algerian Multiple Myeloma Registry) belongs to the SAHTS (Algerian Society of Hematology), was created in 2014 after obtaining the approval of the Ministry of Health. The objectives of this register are: - Obtain reliable epidemiological data - Describe the profile of Algerian patients (pts) - To have an analysis of the diagnostic approaches in all the hematology departments - And measure diagnostic and prognostic difficulties. The AMMR is a prospective, observational, multicenter study. Materials and methods: With the support of a contracted clinical research company, we developed a 19 pages case report form (CRF) which registered all newly pts with MM, plasmocytomas. The main registered variables at diagnosis are patient demographics, disease characteristics, complications, biology, imaging, diagnosis, prognosis and only one item on treatment. All hematology services (17) participated in the study with the help of 23 investigators to inform the CRF. The diagnostic criteria used are those of the IMWG 2003, the prognosis is evaluated according to the classification of Salmon and Durie and the International Staging System. Results: Thus, 1010 pts are collected during these 2 years, 505 men and 505 women. The median age is 63 years (29-100 years), 53% are under 65 years, 13% under 50 years and 18% more than 75 years old. The age-standardized incidence rate (world population WHO 2000-2025) of MM for the year 2015 is 1.71 / 105 inhabitants (1.75 for men and 1.68 for women). In this series: 975 pts (96.53%) are secreting MM and 20 non-secretory MM(1.98%), 4 plasmocytoma (0.40%) and 2 plasma cell leukemias (0.20%). According to the geographical distribution, 62% of the patients are in the middle of Algeria, 19% of the western region and 19% of the eastern region. Among the risk factors for the occurrence of MM, a MGUS is found in 16 pts, a professional activity at risk in 96 pts of which 57 workers of the earth. The clinical feature at diagnosis is dominated by bone syndrome since 92% have bone symptoms, pain in 80.4% of cases and pathological fractures for 96 pts (12%). Neurological signs related to medullary compression are described in 89 pts, anemia is the second complication (56% of the pts). Biological characteristics, the immunological type are IgG type in 50.67% of cases, IgA in 26.36%, light chains in 21.64% of the secreeting MM. All the pts are classified according to the classification of Salmon and Durie, 82% are stages III and 13% of the stages II, among them 24% are classified B. The ISS classification is used in 72% of the pts, with 16.21% stage I, 18.56% stage II and 36.92% stage III. Flow cytometry is performed only in 45 pts (4.5%) and cytogenetics in only one patient. Comments and conclusion: This study shows that the number of pts with MM is important in our country: more than 1000 in 2 years, whereas the previous data did not exceed 350 pts/year. The median age is 63 years, with 53% under 65 years candidates for therapeutic intensification. On the other hand the incidence is 1.71 higher than the two previous studies; this is explained by the rigor of the prospective studies but not by an increase of the frequency. The data collected still show pts diagnosed later (82% stage III) with complications. We deplore the lack of genetics study for our pts. The AMMR is the first hematological malignancy registry in Algeria, is a reliable data bank, which will allow us to claim more diagnostic, pronostic assessment and care for our pts. Disclosures No relevant conflicts of interest to declare.

Deformation and Recrystallised Texture Evolution and the Followed Mechanical and Electrical Properties of Drawn and Annealed Copper Wires - Fyaçal Baira; Mosbah Zidani; Hichem Farh; Salim Messaoudi; Toufik Ziar; Anne Laure Helbert; Thierry Baudin (International Journal of Engineering Research in Africa, 2017)
Copper destined for electrical cabling require a compromise of mechanical properties and electrical resistivity. The drawing process accompanied by the formation of crystalline defects, such as gaps and dislocations, which leads to the increase in hardness, and therefore to the increase in resistivity, a very important characteristic for the conductivity and the efficiency of the cable. The scope of this work is to investigate the phenomenon of deformation texture evolution while copper wire drawn destined for electric cable-making and to understand its relationship with the electrical conductivity. In this study, we notice that the hardness and the resistivity increase with an increase of the deformation level. On the other hand, a slight decrease in the resistivity of the wires was observed after a holding time of 30 min at 260°C. The annealing of wires at 260°C for 9 min of holding time leads to a recrystallisation especially for high deformations and a gradual return of the mechanical properties and of the microstructure towards a state close to the state of the wire rod with the extension of time . The recrystallization texture is composed of the same components as the drawing texture, fibers <111>//ND (Normal Direction) and <001>//ND. The decrease in the intensity of the fiber after annealing is observed. On the other hand, the fiber <001> // ND remains stable.

Effet de l’administration de chlorure de nickel associe avec le selenium sur les paramètres hematologiques et la glande surrénale chez le rat wistar - Asma Saouli (les 14ème journées nationales du département de pharmacie :les méthodes d’analyse de l’industrie pharmaceutique et en milieu Hospitalier.26,27/04/, 2016)

Effet de l’administration de chlorure de nickel associe avec le selenium sur les paramètres hematologiques et la glande surrénale chez le rat wistar - Asma Saouli; Ounassa Adjroud; Boulila, Ismahène; Salah, imene; Anfal Fedala (les 14ème journées nationales du département de pharmacie :les méthodes d’analyse de l’industrie pharmaceutique et en milieu Hospitalier.26,27/04/, 2016)

Hexavalent Chromium-induced Changes in Biochemical Parameters of Wistar Albino Rats - Ounassa Adjroud (International Conference on Biological and Chemical Processes (ICBCP), 25-26 April, 2016)
Potassium dichromate (K2Cr2O7) is one of the most toxic elements to which man can be exposed at work or in the environment. The purpose of the current work is to compare the effect of K2Cr2O7 using variations in the dose, route of administration and duration of exposure in male and female Wistar albino rats with a special focus on biochemical parameters. K2Cr2O7 was subcutaneously administered alone (10, 50 and 100 mg/kg body weight) to female Wistar albino rats. Male rats received in their drinking water K2Cr2O7 30 mg/L/day) for 20 consecutive days. The Biochemical parameters were evaluated on days 3, 6 and 21 after subcutaneous (sc.) treatment in female rats and on days 10 and 20 after oral administration in male rats. The subcutaneous (s.c.) administration of 25 mg/kg of K2Cr2O7 to Wistar albino rats induced a slight change in plasma glucose levels during the experiment period. On the contrary, a significant decrease in plasma glucose levels was observed with 50 mg/kg mainly on days 3 (-26%) and 21 (-48%) after treatment compared to controls females rats. On the other hand, the higher dose provoked a significant increase in plasma glucose concentrations on days 6 (+31%) and 21 (+60%). similarly, the lower dose of chromium had no effect on the plasma urea levels. Conversely, a significant increase (122%) in this parameter was obtained during the first three days after treatment. In addition, a significant decrease in plasma glucose levels was observed with 50 mg/kg mainly on days 3 (-26%) and 21 (-48%) after treatment. On the other hand, the higher dose provoked a significant increase in plasma glucose concentrations on days 6 (+31%) and 21 (+60%). similarly, the lower dose of chromium had no effect on the plasma urea levels. Conversely, a significant increase in this parameter (122%) was obtained during the first three days after treatment. In addition, administration of 100 mg/kg of K2Cr2O7 by s.c markedly augmented the levels of plasma urea on days 3 (62%) and 6 (121%). Administration of 30 mg/L/day of K2Cr2O7 in the drinking water induced a significant augmentation in both of plasma glucose (27%) and urea (126%) during the first ten days of treatment. These results suggested that K2Cr2O7 administered subcutaneously or in the drinking water may induce harmful effects on biochemical parameters. Keywords : glucose, potassium dichromate, Wistar albino rat, urea.

Effets de l'administration par voie sous- cutanée du nickel associe avec le zinc et le selenium sur l'uremie et le determinisme de la reproduction chez les rates gestantes - Imane Salah; Ounassa Adjroud; Ismahene BOULILA; Anfal Fedala; Asma Saouli (Premier colloque International de Toxicologie et Santé. 28-29 novembre, 2016)

Evaluation du rpotocole R C2H2OPA dans le lymphome médiastinalprimitif à grande - F Kacha; F Soltani; M Aiche; M Saidi (Congrès maghrébin d'Hématologie , Mai, 2016)

Lymphome osseux primitif ;à propos d’un cas - F Kacha (Congrès maghrébin d'Hématologie , Mai, 2016)

Lymphome osseux primitif ;à propos d’un cas - F Kacha; F Soltani; M Aiche; M Saidi (Congrès maghrébin d'Hématologie , Mai, 2016)

LNH à grandes cellules B et foie - M Aiche; F Soltani; F Kacha; M Saidi (Congrès maghrébin d'Hématologie , Mai, 2016)

Evaluation des réponses moléculaires chez des patients atteints de LMC traités par IMATIB en première intention - F Kacha; F Soltani; M Aiche; M Saidi (Congrès maghrébin d'Hématologie , Mai, 2016)

Aspects épidémiologique et clinique du lymphome diffus à grandes cellules B selon les facteurs de l’index pronostique international (IPI) - M Aiche; F Soltani; M Saidi (Congrès maghrébin d'Hématologie , Mai, 2016)

Evaluation des réponses moléculaires chez des patients atteints de LMC traités par IMATIB en première intention - F Kacha; F Soltani; M Aiche; M Saidi (Congrès maghrébin d'Hématologie , Mai, 2016)

Description des effets secondaires liés àl’Imatib dans la leucémie myeloide chronique - F Kacha; F Soltani; M Saidi (Congrès maghrébin d'Hématologie , Mai, 2016)

Description de deux cas de LMC précédés de tumeur solide - F Kacha; F Soltani; M Saidi (Congrès maghrébin d'Hématologie , Mai, 2016)

Contribution à l’étude de la biodiversité entomologique de l’Abricotier dans la région de Batna-Algérie - CHAFAA Smail (10th Maghrebian Congess on Marine Sciences and the 5th Franco-Maghrebian Congress of Zoology & Ichthyology, 2016)

Contribution à la recherche des effets du nickel administré par voie sous-cutanée et son éventuelle interaction avec le sélénium et le zinc sur la leucopoïèse et l’histologie hépatique - Anfal Fedala; Ounassa Adjroud; Salah, Imène; Asma Saouli; Boulila, Ismahène (Les 14 èmes journée nationales de département de pharmacie –.les méthodes d’analyse en milieu hospitalier,état des lieux et perspectives d’avenir, 27 _28 Avril, 2016)

Effet d’administration du chlorure de nickel associé avec le sélénium sur les paramètres hématologiques et la glande surrénale chez le rat wistar - SAOULI ASMA (Les 14 èmes journée nationales de département de pharmacie –.les méthodes d’analyse en milieu hospitalier,état des lieux et perspectives d’avenir, 27 _28 Avril, 2016)

Effets de l'administration par voie sous- cutanée du nickel associe avec le zinc et le selenium sur l'uremie et le determinisme de la reproduction chez les rates gestantes - Salah Imane (Premier colloque International de Toxicologie et Santé. 28-29 novembre, 2016)

Hexavalent Chromium-induced Changes in Biochemical Parameters of Wistar Albino Rats - Ounassa Adjroud (Engineering for Life Sciences and Biomedicine" April 25-26, 2016, 2016)

Etude épidémiologique nationale des LAL - Z Zouaoui; M Benlazar; M Bachiri (Revue Algérienne d'Hématologie, 2016)

Outbreak of OXA-48-Producing Klebsiella pneumoniae Involving aSequence Type 101 Clone in Batna University Hospital, Algeria. - Lotfi Loucif; Ahmed Kassah-Laouar; Mahdia Saidi; Amina Messala; Widad Chelaghma; Jean-Marc Rolain (Antimicrobial Agents and Chemotherapy, 2016)
<nav data-core-nav="article"> <header> Seven nonredundant ertapenem-resistant Klebsiella pneumoniae isolates were collected between May 2014 and 19 January 2015 in the nephrology and hematology units of Batna University Hospital in Algeria. All strains coproduced the blaOXA-48, blaCTX-M-15, blaSHV-1, and blaTEM-1D genes. Six of these isolates belonged to the pandemic clone sequence type 101 (ST101). The blaOXA-48 gene was located on a conjugative IncL/M-type plasmid. This is the first known outbreak of OXA-48-producing K. pneumoniae isolates involving an ST101 clone in Batna University Hospital. </header> </nav>

Descriptive Study of Diffuse Large B Cell Lymphoma in Algeria and Tunisia over a Period of 5 Years - N Boudjerra; S Oukid; Abad, MT; C Aboura; L Louanchi; M Ramaoun; M Belhani; M Allouda; H Aftisse; H Ait-Ali; R Ben lakhal; B Meddeb; et al. (Blood, 2016)
Background: Diffuse Large B Cell Lymphoma (DLBCL) is the most common form of aggressive non-Hodgkin's lymphoma (NHL) accounting for approximately 40 % of all NHL cases. The aim of our study is to carry out an epidemiologic description and to compute the incidence of DLBCL in 2North African countries, Algeria and Tunisia. Patients and methods: This is a multicenter retrospective and descriptive study, covering a period of 5 years (January 2010 - December 2014), carried out in 17 centers in Algeria and 5 centers in Tunisia. Patients aged less than 15 years were excluded. We used the classification of World Health Organization. We used Epi info 6 software to analyze the data. Results: 1432 cases were identified, 1175 in Algeria and 257 in Tunisia. The sex distribution of DLBCL was as follows: males 837 (58.4 %), females 591 (41.6 %), male-to-female ratio 1.40. The age of patients ranged from 16 to 96 years (median 52 years) and 64.2 % of the patients are less than 60. The incidence estimates for the years 2012 and 2013 are respectively 0.86 and 0.87 for 100,000 inhabitants. The most frequent occupation of the cases is farmworker (11.5%). The average time between the date of diagnosis and clinical examination is 31 days. The average delay between the first clinical sign and the date of diagnosis is 133 days. A familial history of cancer is found in 10% of the cases. The lymph node biopsy was undertaken in 30.7% of the cases in the cervical area and in 15% of cases in the mediastinal area. A reexamination of the slides was undertaken in 20% of cases while 61.6% of them were found to be advanced clinical stages (III + IV). Splenomegaly was found in 16% of the cases and hepatomegaly in 7%. ORL damage was found in 16% of the cases and marrow infiltration in 10.2%. A Prognostic Score IPI ≥ 2 is found in 38% of the patients. Comments: On a previous Algerian study concerning all lymphomas diagnosed over a period of 6 years (2007-2012) (Journal of Hematology No. 10-11, 2015), 485 new cases of lymphoma were diagnosed on average per year. In the present study, the average number of new cases of DLBCL was 235 and the average proportion was 48% of all lymphomas. It should be emphasized that all cases underwent an immunohistochemical study and that lymphatic cases were excluded (digestive, bone, skin). The national incidence rate is low compared to that of international studies, a fact that is probably due to difficulties in the diagnosis including lack of implementation of immunohistochemistry techniques in our region. Disclosures No relevant conflicts of interest to declare.

Epidemiology of Extranodal Diffuse Large B Cell Lymphomas in Algeria: A Study of the Algerian Group of Extranodal Lymphomas (GALEG) - Hamdi, S; I Bentahar; H Harbadji; Fatiha Grifi; S Bougherira; T Filali; M Allouda; N Mesli; B Berber; K Bouzid; R Sai; Hamladji, RM; et al. (Blood, 2016)
Introduction: Primitive extranodal lymphomas are a heterogeneous group of malignant lymphoid hematological developed from the mucosa-associated lymphoid tissue (MATL) or sites that have acquired MALT after repeated stimulation. The particularity of this type of affection reside: the access to diagnosis which is difficult and therapeutic approach which respond to the ATB, antiviral, surgery and RT. They represent 24-48% of lymph node lymphomas and they are increasing. The incidence of lymphoma is growing in the world, it is approximately 16.8 / 105inhabitants. In Algeria in 2012, the incidence of lymph node lymphomas in adults was 2.24 / 100,000. Lymphomas Diffuse large B-cell phenotype (DLBCL) represent 50-60% of lymphomas, it is the most common histological type. Goals of the study: 1-analyze the epidemiological characteristics (gender, age, geographical distribution, annual incidence). 2- Identify anatomical sites. 3- Specify the clinical and prognostic features Patients and methods: It's is a multicenter, retrospective study over a period between 2010-2014. The study population included all pts over 15 years and having an extranodal DLBCL at 18 hematology centers and 4 cancer centers. Data were collected on data sheets distributed to the various services involved in the study. The diagnosis is made on the histological examination of a biopsy of the affected organ. The clinical, biological and imaging results allowed us to classify and identify prognostic factors for pts. Results: Among 1057 sheets of extranodal lymphomas, the type DLBCL is specified in 562 (53%) cases, distributed in 325 men and 237 women (sex ratio M/F: 1.36). The average age at diagnosis is 51 years (16-88) with a peak in the age group 50-60 years. The overall annual incidence of 0.31/105 inhabitants/year and the specific incidence for patients over 15 years is 0.42 / 105inhabitants/year. PS 0-1: 323 / 543pts (60%). Number of pts (pts) by place of care: Annaba 65, Sétif: 60, CAC Constantine: 53, Tizi Ouzou: 49, Blida Cac: 41, CMPC-hematology: 40, Tlemcen: 30, Beni- Méssous- hematology: 29, CAC CPMC: 24, EHUOran: 23, hematology CAC Batna: 22, CHU Oran: 19, HMRUO: 17, Blida-hematology: 16, HCA:16, SBA: 15, CAC Béni-Messous: 14, EPH Mascara: 10, HMRU Oran: 9, Bejaia: 7, hematology CHU Batna: 2, hematology Cne:1. Number of cases according to anatomical localisation: Stomach: 180, Intestine: 31, Colon 12, Tonsils: 70, Cavum: 31, nasal cavities: 11, Bones: 43, mediastinum: 41, SNC: 29, Skin: 25, Rate / MO :15, Thyroid: 12, soft Parties: 10, Breast: 6, lung / pleural: 5, Liver: 5, Others: 36. The clinical symptomatology is very heterogeneous, specifically of the affected organ. Clinical stage is specified in 549 cases, according to Ann Arbor: SCIE: 272 (49%), SCIIE: 149 (27%), SCIIIE: 31 (6%), SCIV: 97 (18%). The International Prognostic Index adjusted for age (IPIaa) include: for pts less than 60 years: Low (F): 70 (23%), lower intermediate (IF): 130 (43%), intermediate high (IE) : 69 (23%), high (H): 32 (11%); for over 60 years Topics: F: 33 (23%), MI: 53 (37%) IE: 41 (28%), E: 17 (12%). Comments: As with other types of lymphoma, there is a male predominance and a peak incidence in the age group 50-60 years. The higher number of pts in the center and east of the country is probably related to a denser population in these regions. The histological type DLBCL at 53% is in agreement whith what it is conventionally reported. The incidence of 0.31/105inhabitants/year extranodal DLBCL is lower than the overall nodal DLBCL, however, the incidence of extranodal NHL is rarely determined. The number of cases of extranodal lymphomas described in this study is certainly below the actual number because this group of disorders is supported by various specialties related to the location of lymphoma. Extranodal lymphomas has a clinical polymorphism, but it is recognized that gastric and tonsillar locations are the most common, the other despite their rarity, require attention from management. This type of lymphoma is characterized by a preponderance of localized stages unlike ganglion lymphomas where the extended stages predominate. Likewise distribution by IPIaa not exceeding one pejorative factor is more common. Conclusion: Extranodal DLBCL are rare, they are characterized by a diversity clinicopathological that challenges us to homogenization of their treatment in multidisciplinary level. Disclosures No relevant conflicts of interest to declare.

Epidemiological Approach of Chronic Myeloid Leukemia. Algerian-Tunisian Study - Djouadi, K; Abdennebi, N; Harieche, F; R Ahmed-Nacer; Hamladji, RM; Bouchakour, A; Taoussi, S; Abad, MT; Touil, Fz; Hamdi, S; S Bougherira; Fatiha Grifi; et al. (Blood, 2016)
Introduction: Chronic myeloid leukemia (CML) accounts for 7%-15% of all leukemias affecting adults. The incidence in Algeria is 0.4/100,000 inhabitants in 2009. The aim of this study is to establish an Algerian-Tunisian epidemiological approach of CML and to know the characteristics of the disease in both countries. Materials and methods: This is a retrospective, longitudinal and multicenter study, including Algerian and Tunisian patients with CML diagnosed between January 2010 and December 2014. Through a data form distributed to various hematology departments, we collected and analyzed the following information: Patient's general characteristics, profession, circumstances of discovery of the disease, clinical and para-clinical examinations outcomes at the time of diagnosis including blood count, blood smear, bone marrow aspiration, cytogenetics, molecular biology, stages of the disease and the Sokal and Eutos prognostic classification scores. Bio-statistical tests: incidence, prevalence and rate of prevalence or relative prevalence (reported to 100,000 inhabitants / year). The descriptive analysis of quantitative and qualitative variables as percentages and 95% confidence interval. The Chi2 test is used to compare two variables. Results: We collected 1349 cases, including 325 from 06 Tunisian hematology units and 1024 from 18 Algerian units. The incidence in the Algerian-Tunisian population was 0.67/100,000 inhabitants with a prevalence rate of 2.72/100,000 inhabitants. The incidence in Tunisia was 0.50 / 100,000 inhabitants with a prevalence of 227 cases in 2014. In Algeria the incidence was 0.53/100,000 inhabitants with a prevalence of 1030 in 2014. The median age is 48 years (03-90) with a peak incidence in the age group (45-49 ans) and slight male predominance (sex ratio: 1,2). There was any notion of risk exposure. The average time between the start of the unrest and the date of diagnosis is 127 days (1-667). The circumstances of discovery: fortuitous in 30.5% (n = 355), splenomegaly in 39.7% (n = 463), asthenia in 24.6% (n = 287), a complication in 8.4% (n =95). Clinical examination includes general signs in 424 cases (36.4%): Weight loss 22.6% (n = 263), profuse sweating 13.8% (n = 13, 8%), bone pains found in 7.8%, splenomegaly in 81.7% (n = 952) with an overhang splenic average of 11.5 ± 5.3 cm (1-28), cutaneous and subcutaneous bleeding: 13.5% (n = 97), thrombosis 0.9% (n = 09). Biological characteristics: the Complete blood count (n = 1185) shows a white blood cells average rate of 171,223 G/L (34,700-984,800), hemoglobin average rate of 10.2 g/dl (4-17), platelets at 394,070 g/l (85-1340). Blood smear 96.3% (n = 1121): the average myelemia was 43.2% (10-98%). The Myelogram is practiced in 55% (n = 641), the average rate of the granular 76,5% (40-99%), erythroblasts 10.5% (0-82%), average blasts 3.6%. The karyotype 38.1% (n = 444), the Philadelphia chromosome was found in 423 cases (95, 3%); additional abnormalities were found in 17 cases (3.8%). The Fish was practiced in 281 cases (24.1%) and transcribed bcr/abl was found in 257 cases (91.4%). Molecular biology is practiced in 672 cases (57.7%) the transcript bcr/abl is found in 100%, the transcript of the type is specified in 373 cases, it is kind of b2a2 in 159 cases (42.6%), a b3a2 type in 180 cases (48.3%) and other transcribed in 34 cases (9.1%). CML chronic phase is diagnosed in 88.8% (n = 1051), acceleration phase in 9% (n = 107) acutisation phase in 3.1% (= 37). The distribution of pts according to Sokal prognostic classification (n = 948) describes a predominance of intermediate risk in 54% (n = 511), high risk in 30.3% (n = 287) and low risk in 16% (n = 152). The Eutos score is specified in 769 cases (66%), it is less than 87 in 661 cases (86%) and more than 87 in 108 cases (14%). Conclusion: The incidence of CML in the Algerian-Tunisian population is 0.67/100,000 population with a prevalence rate of 2.72/100,000 inhabitants. The young adult is more affected with a peak incidence between 45 and 49. The average time between the onset of the disease and the diagnosis remains long and the delay probably explains the frequency of tumor forms encountered in Algeria and the prevalence of high and intermediate risk, according to Sokal prognostic classification. Disclosures No relevant conflicts of interest to declare.

Spectrophotometric Determination of Chromium, Copper, Nickel and Iron in Electroplating Hydroxide Sludges - M Boudjouada; Salhi Ramdane; S Bekhbekh; A Kabouche; N Gherraf (Asian journal of Chemistry, 2016)

Recovery of nickel and copper from metal finishing hydroxide sludge by kinetic acid leaching - Salhi Ramdane; M Boudjouada; S Messikh; N Gherraf (Journal of New Technology and Materials, 2016)

Epidemiological approach of chronic myeloid leukemia. Algerian-tunisian study - Djouadi, K; Abdennebi, N; Harieche, F; R Ahmed-Nacer; Hamladji, RM; Bouchakour, A; Taoussi, S; Abad, MT; Touil, Fz; Hamdi, S (American Society of Hematology Washington, DC, 2016)

X-Ray diffraction study on the criystal structure of [(H3O)Nd(SO4)] - BENSADEK Ali (CACPM3C. 19-21 Mai, 2015)

Oxonium Lanthanide double sulfate terahydrates - BENSADEK Ali (The first Conference on Mechanical, Energy and Material Engineering, CMEM 8&9 Décembre, 2015)

Synthèse et caractérisation des photosensibilisant de type xanthènes - Zouchoune Soria (13èmes journée de Pharmacie, 27 & 28 Mai, 2015)

BOUES RESIDUAIRES DE L’INDUSTRIE DES TRAITEMENTS DE SURFACES: ANALYSE DES METAUX PAR SPECTROPHOTOMETRIE - Salhi Ramdane (IX émes journées internationales de chimie 08-09 Novembre, 2015)

ETUDE DE L’INHIBITION DE LA CORROSION D’ACIER DOUX PAR DES COMPOSES ORGANIQUES A BASE TRIAZOLE EN MILIEU ACIDE - Salhi Ramdane (IX émes journées internationales de chimie 08-09 Novembre, 2015)

Spectrophotometric Method for the Determination of Copper, Nickel, Chromium and Iron in Electroplating Hydroxide Sludges - Salhi Ramdane (First International Conference on Applied Chemistry (ICAC 2015) "Chemistry for Sustainable World" , November 18- 19, 2015)

Interaction between NiCl2 and Selenium on Energy Profiles in Wistar albino Preimplanted Rats - Ounassa Adjroud (International Conference on Biological and Life Sciences. April 13-15, 2015)

Nephroprotective Effects of Selenium against Nickel Chloride-Induced Nephrotoxicity in Pregnant Rats - Ounassa Adjroud (5th International Conference on Environment Science and Engineering, 2015)

Epidemiology and Clinical Features of Chronic Lymphoid Leukemia. Review of the Algerian Chronic Lymphoid Leukemia Study Group - N Dali; H Ait-Ali; A Tibiche; F Belhadri; Harieche, F; R Ahmed-Nacer; Hamladji, RM; Taoussi, S; S Oukid; Abad, MT; N Boudjerra; M Belhani; et al. (Blood, 2015)
Introduction: Chronic lymphocytic leukemia (CLL) is the most frequent leukemia of the adult in Europe and North Africa. It is rare on the Asian and African continents. It affects mainly elderly people over 60 years. The main objective is determining the rate of average annual incidence, and secondly establishing the distribution of this complaint according to the different health regions of the country and precise the epidemiological characteristics. Patients and Methods: It is a national, descriptive, retrospective epidemiological study carried out for a period of 05 years : from January 2009 to December 2013. Information collection is done thanks to the setting up of a technical data sheet sent out to the appropriate services. This technical data sheet is about the geographic data of the patient (place of birth, place of residence, place of taking charge of the disease and the date of the diagnosis), anthropologic data (age at the diagnosis, sex), as well as the clinico-biological data. The working of the responses was done on SPSS 19 .0. In our study, the diagnosis is carried before an hyperlymphocytosis > 5000/ mm3, a cytological examination of the blood smear and an immunophenotyping operation by cytometer operation in flow. Results: 17 hematology departments have participated in this study with 1210 cases listed, of which 68,1% (824 pts) are men. The average annual recruitment is of 242 cases. The average annual incidence rate, calculated according to the data of the national statistics office is estimated at 0,66 / 100.000 inhabitants.This incidence does not increase over the years and stays relatively stable (2009 = 0,67; 2010 = 0,57; 2011 = 0,63; 2012 = 0,67; 2013 = 0,74/100.000 inhts). The geographic distribution of the pts according to their places of residence, shows that the majority among them are from the north of the country particularly the center (0,80/100.000 inhts). Incidence increases over age, going among men from 0,06 for 100.000 inhts between 30 - 39 years to 11,94 / 100.000 inhts at 80 years and over and among women from 0,04 for 100.000 inhts to 6,08 for 100.000 inhts. The average incidence rate is of 0,85/100.000 inhts among men and of 0,42/100.000 inhts among women. The average age at the diagnosis is of 67,5 years (33 - 98 years). 30,1% (365 pts) incident cases are observed among the patients over 75 years and 14,1% (171 pts) among the patients below the age of 55 years. The profession that is most found is farming 12.2% (78/635 precised). The diagnosis is late in Algeria, the first symptome which brings the patient to consultation is the tumoral syndrome (44% (363 / 825 precised)) in an average diagnosis period of time of 07 months (01 - 96 months). The stage C (classification of Binet) is equally predominant, found in 41,1% (492 / 1172 precised). In terms of biology : the average rate of lymphocytes is of 92500/mm3 (5000-900 000/mm3). The morphological study on blood smear finds 88,2% (1066 / 1208 precised) of typical CLL and 50% of Gambrest cells. The cytometer operation in flow done in 746 cases (61,6%) shows a score of matutes > 4 in 92,3% and in 7,7% is equal to 3. the cytogenetic operation (Caryotype and Fish) done in only one hematology department (CAC of Blida) among 102 patients (8.4%). Comments: The rate of incidence in Algeria is weak compared to that of other countries. The rate of incidence standardized to the world population is of 0,52 cases/100.000 inhts and to the European population is of 0,68 cases p 100.000 inhts. The young age of the population may explain this incidence and that some patients at the stage A are not diagnosed. The CLL affects more frequently men. The average age at the diagnosis is of 67,5 year. However, 30,1% of the incident cases are observed among the patients over 75 years in Algeria versus 45 à 50% of incident cases in Europe and this may be explained by the young age of our population. The CLL are placed 5th among the malignant hemopathies: the rate of incidence for the year 2009 : LNH = 1.96; LH = 1.2; MM = 0.96; AML = 0.85; CLL = 0.67; CML = 0.44; ALL = 0.32. Conclusion: the CLL can be diagnosed and differentiated from the other lymphoproliferative syndromes thanks to the morphological examination of the lymphocytes at the blood smear completed by an immunophenotyping operation of the peripheral blood . This study represents only an epidemiological approach of the CLL in Algeria. The incidence is still weak in our country; it affects as in the other countries the elderly people with a masculin predominance. Disclosures No relevant conflicts of interest to declare.

Spatiotemporal diversity, structure and trophic guilds of insect assemblages in a semi-arid Sabkha ecosystem - Haroun Chenchouni; Taha Menasria; Souad Neffar; Smail Chafaa; Lyès Bradai; Rachid Chaibi; Mohamed-Nacer Mekahlia; Djamel Bendjoudi; Abdelkrim SI-BACHIR (PeerJ, 2015)
The current study highlights some knowledge on the diversity and structure of insect communities and trophic groups living in Sabkha Djendli (semi-arid area of Northeastern Algeria). The entomofauna was monthly sampled from March to November 2006 using pitfall traps at eight sites located at the vicinity of the Sabkha. Structural and diversity parameters (species richness, Shannon index, evenness) were measured for both insect orders and trophic guilds. The canonical correspondence analysis (CCA) was applied to determine how vegetation parameters (species richness and cover) influence spatial and seasonal fluctuations of insect assemblages. The catches totalled 434 insect individuals classified into 75 species, 62 genera, 31 families and 7 orders, of which Coleoptera and Hymenoptera were the most abundant and constant over seasons and study stations. Spring and autumn presented the highest values of diversity parameters. Individual-based Chao-1 species richness estimator indicated 126 species for the total individuals captured in the Sabkha. Based on catch abundances, the structure of functional trophic groups was predators (37.3%), saprophages (26.7%), phytophages (20.5%), polyphages (10.8%), coprophages (4.6%); whereas in terms of numbers of species, they can be classified as phytophages (40%), predators (25.3%), polyphages (13.3%), saprophages (12%), coprophages (9.3%). The CCA demonstrated that phytophages and saprophages as well as Coleoptera and Orthoptera were positively correlated with the two parameters of vegetation, especially in spring and summer. While the abundance of coprophages was positively correlated with species richness of plants, polyphage density was positively associated with vegetation cover. The insect community showed high taxonomic and functional diversity that is closely related to diversity and vegetation cover in different stations of the wetland and seasons.

Nephroprotective Effects of Selenium against Nickel Chloride-Induced Nephrotoxicity in Pregnant Rats - ADJROUD OUNASSA (International Proceeding of Chemical, Biological & Environment, 2015)

Effet d’administration du chlorure de nickel associé avec le sélénium sur les paramètres hématologiques et la glande surrénale chez le rat wistar - BOULIA ISMAHENE; Ounassa Adjroud (XIIème Journées de Pharmacie et VIIème Journées de la Douleur 04 et 05 Juin, 2014)

Copper(II) bromide as an efficient catalyst for acetal to bisarylmethyl ether interconversion - RofiaMezaache; Hassina Harkat; Julie Obszynski; Abdelhamid Benkouider; Aurélien Blanc; Jean-Marc Weibel; Patrick Pale (Tetrahedron Letters, 2014)
Transprotection of acetals to bis(methoxyphenyl)methyl (BMPM) ethers can be efficiently achieved in the presence of copper dibromide as catalyst in acetonitrile at room temperature. Acetals are conveniently and selectively converted to the corresponding mono-protected diol with bis(methoxyphenyl)methyl isopropyl ether (BMPMOiPr) as the reagent. This new practical reagent allows the BMPM transfer to 1,3-dioxolanes or 1,3-dioxanes under copper catalysis. The reaction conditions are also very mild and tolerant to various functional groups, including other protecting groups.
Keywords: Acetal; Alcohol; Bis(methoxyphenyl)methyl; Copper; Protecting group; Transprotection

ChemInform Abstract: Zeo-Click Synthesis: Copper-Zeolite-Catalyzed Synthesis of Ynamides. - Hassina Harkat; Sophie Borghèse; Nigris, Matteo; Serguei Kiselev; Valérie Bénéteau; Patrick Pale (Advanced Synthesis & Catalysis, 2014)
Copper(I)-zeolites, especially copper(I)-ultra stable Y zeolite (USY), are very efficient heterogeneous catalysts for the coupling of functionalized 1-bromoalkynes and various nitrogen derivatives. Under these conditions, sulfonylated alkyl- or arylamines and various N-heterocycles, such as oxazolidinones or indoles, could be efficiently transformed into the corresponding N-alkynyl derivatives. However, imidazoles gave addition products rather than coupling products. The reaction conditions proved compatible with a variety of functional and protecting groups. Such zeolitic catalysts can be recycled and reused at least five times without significant deactivation. Low catalyst loading could be used (4 mol%) and as low as 0.8 mol% of this heterogeneous copper catalyst still gave good conversion and yields. <figure> </figure>

Mild, efficient derivatives indole synthesis using USY-CuI zeolite as a reusable catalyst - HARKAT Hassina (XII èmes journees de pharmacie et VII eme journee de lutte contre la douleur 04 et 05 Juin, 2014)

An efficient and reusable catalyst for Von Pechmann reaction - HARKAT Hassina (Sciences d’Interfaces Chimie – Biologie SNSI C-B, 22 et 23 Octobre, 2014)

LES MOLECULES BIOACTIVES ET L'ACTIVITE BIOLOGIQUE DE LA PLANTE BASSIA MURICATA - BOUZGHAIA Badra (XII èmes journees de pharmacie et VII eme journee de lutte contre la douleur 04 et 05 Juin, 2014)

Synthesis of 1,4- dihydropyridines through Hantzsch reaction catalyzed by p- toluenesulfonate complexes of copper (II) - Zouchoune Soria (Sciences d’Interfaces Chimie – Biologie SNSI C-B, 22 et 23 Octobre, 2014)

Sythesis and structural study of hydrogen neodymium sulfate tetrahydrate - BENSADEK Ali (4ème Colloque International de Chimie CIC-4, Batna, 25 -27 Novembre, 2014)

ETUDE PHYTOCHIMIQUE DE L'ESPESE BASSIA MURICATA ET LEUR ACTIVITE BIOLOGIQUE - BOUZGHAIA Badra (4ème Colloque International de Chimie CIC-4, Batna, 25 -27 Novembre, 2014)

SYNTHESES DES HETEROCYCLES AZOTES : 1,4DIHYDRO-PYRIDINE CATALYSEE PAR TOSYLATE DE CUIVRE - Zouchoune Soria (4ème Colloque International de Chimie CIC-4, Batna, 25 -27 Novembre, 2014)

Effet d’administration du chlorure de nickel associé avec le sélénium sur les paramètres hématologiques et la glande surrénale chez le rat wistar - BOULIA ISMAHENE (XIIème journées de pharmacie et VIIème journées de la douleur 04 et 05 juin, 2014)

Influence de la vapeur de gazoline sur la modulation de certaines proteines pulmonaires chez le rat blanc. - Ounassa Adjroud (First International Congress of Biotoxicologie and Bioactivity, 26 and 27 November, 2014)

Nephroprotective Effects of Selenium against Nickel Chloride-Induced Nephrotoxicity in Pregnant Rats - Ounassa Adjroud (ICNSE 2014: April 4-5, 2014)

Inventaire et dynamique globale du peuplement des nématodes phytoparasites (Nematoda : Secernentea) de l’olivier (Olea europeae) dans une région aride du Nord-Est de l’Algérie - Smail Chafaa; Abdelkrim SI-BACHIR; Meriem BOUKHADRA; Asma ACHI (Journal of Animal &Plant Sciences, 2014)
The community of nematodes (Nematoda: Secernentea) in groves of North East Algeria, has been the subject of regular observations of September 2011 to May 2012. Sampling and extraction of nematodes by the buckets technique are conducted following the method of Baermann. The sampling groves are composed by olive trees (Olea europea: Oleaceae) from four varieties: Chemlal, Sigoise, Frontoï and Sévillane. We identified a total of 531 individuals. The systematic inventory revealed 14 genus of Nematoda, belonging to 10 families and 3 orders. The Tylenchida and Dorylaimida are the best represented orders. They represent 92.85% of the total community of all identified nematodes, while Aphelenchida represent only 7.15%. The genus Pratylenchus records alone 54.75% on the Sévillane variety and 33.02% on the Frantoi variety. The most represented genus on Sigoise and Chemlal varieties is Meloidogyne with respectively 43.24% and 30.43%. Grove of Sévillane variety hosts the highest abundance of nematodes with 57.44%; against only 19.96%, 13.94% and 8.66%, respectively, for the varieties Frantoi, Sigoise and Chemlal. Depending on the seasons, nematodes are more abundant in autumn (88.52%) than in winter (8.66%) and the spring (2.82%). Pratylenchus and Meloidogyne are noted with large numbers, especially in winter.

Copper(II) bromide as an efficient catalyst for acetal to bisarylmethyl ether interconversion - RofiaMezaache; Hassina Harkat; Julie Obszynski; Abdelhamid Benkouider; Aurélien Blanc; Jean-Marc Weibel; Patrick Pale (Tetrahedron Letters, 2014)
Transprotection of acetals to bis(methoxyphenyl)methyl (BMPM) ethers can be efficiently achieved in the presence of copper dibromide as catalyst in acetonitrile at room temperature. Acetals are conveniently and selectively converted to the corresponding mono-protected diol with bis(methoxyphenyl)methyl isopropyl ether (BMPMOiPr) as the reagent. This new practical reagent allows the BMPM transfer to 1,3-dioxolanes or 1,3-dioxanes under copper catalysis. The reaction conditions are also very mild and tolerant to various functional groups, including other protecting groups.

Zeo-Click Synthesis: Copper-Zeolite-Catalyzed Synthesis of Ynamides - Hassina Harkat; Sophie Borghèse; Matteo De Nigris; Serguei Kiselev; Valérie Bénéteau; Patrick Pale (ADV SYNTH CATAL, 2014)
Copper(I)-zeolites, especially copper(I)-ultra stable Y zeolite (USY), are very efficient heterogeneous catalysts for the coupling of functionalized 1-bromoalkynes and various nitrogen derivatives. Under these conditions, sulfonylated alkyl- or arylamines and various N-heterocycles, such as oxazolidinones or indoles, could be efficiently transformed into the corresponding N-alkynyl derivatives. However, imidazoles gave addition products rather than coupling products. The reaction conditions proved compatible with a variety of functional and protecting groups. Such zeolitic catalysts can be recycled and reused at least five times without significant deactivation. Low catalyst loading could be used (4 mol%) and as low as 0.8 mol% of this heterogeneous copper catalyst still gave good conversion and yields.   <figure>   </figure> <img alt="image" data-lg-src="/cms/asset/eeb06caa-463b-49ed-b08e-81c7bc1d1d59/mcontent.jpg" loading="lazy" src="https://onlinelibrary.wiley.com/cms/asset/0a7ef62a-c89a-4034-a7dd-1c736bd3a478/mcontent.gif" title="image">

The toxic effects of nickel chloride on liver, erythropoiesis, and development in Wistar albino preimplanted rats can be reversed with selenium pretreatment - Ounassa Adjroud (Environmental toxicology, 2013)
The exposure to nickel chloride (NiCl2) can cause hematotoxicity and hepatotoxicity and canaffect development. The present study pertains to the protective effect of selenium (Se) against NiCl2-induced toxicity in preimplanted Wistar albino rats. The subcutaneous (s.c.) administration of 25 or 50 mg/kg of NiCl2 to Wistar albino rats on day 3 of gestation induced an immediate and significant decrease in maternal body weight and anemia 2 days after treatment. In addition, an increase in plasma aspartate aminotransferase (AST) was observed. These effects were maintained on day 20 of gestation. Moreover, a significant increase in plasma alanine aminotransferase (ALT) levels was observed with the administration of 25 mg/kg of NiCl2. Conversely, administration of 50 mg/kg of NiCl2 by s.c. injection increased erythropoiesis at day 20 of gestation and decreased platelets counts. In addition, administration of 100 mg/kg of NiCl2 markedly reduced the maternal body weight and number of live fetuses and increased fetal loss, predominantly at the end of the experimental period. All dose levels of NiCl2 caused an alteration in the hepatic histoarchitecture. When 0.3-mg/kg Se was injected s.c. with 100-mg/kg NiCl2, the levels of plasma AST and ALT and the structure of the liver were restored. Administration of 20 mg/L/day of NiCl2 in the drinking water significantly reduced the maternal body weight at day five of gestation as well as erythropoiesis during the exposure period. The present study suggests that Se can counteract the nocuous effect of nickel on the liver; however this antioxidant did not prevent alterations in development and erythropoiesis. © 2011 Wiley Periodicals, Inc. Environ Toxicol 2013.

Antagonistic Role of Selenium against Hepatotoxic Effects of Nicl2 in Preimplanted Wistar Albino Rats - Ounassa Adjroud (Sixth International Conference on Environmental Mutagens in Human Populations, Mars, 2012)
Nickel, a potent toxic metal, is very harmful to the environment and to humans because of its in vivo accumulation in liver. The present study was conducted to investigate the protective effect of selenium (Se) against nickel toxicity on liver function in preimplanted Wistar albino rats. NiCl2 was given on day three of pregnancy either in distilled drinking water at a dose of 20 mg/L/day) for 16 consecutive days or as a single s.c. dose of 25, 50, or 100 mg/kg. Se was given as an s.c. injection (0.3 mg/kg) together with the higher dose (100 mg/kg) of NiCl2. Changes in plasma glucose, triglycerides and total cholesterol were measured in treated and control groups on days five and 20 of gestation. NiCl2 s.c. induced on day five of gestation showed a significant (<0.05) decrease in plasma triglycerides, with a dose of 100 mg / kg (-48 percent). This decrease was maintained at day 20 of gestation with doses of 50 mg / kg (-36 percent) and 100 mg / kg (-31 percent). In contrast, the low dose induced an increase of + 50 percent in plasma triglyceride compared to controls. In addition, NiCl2 s.c. caused on day five of gestation a significant decrease (p <0.05) in plasma total cholesterol with the low (-50 percent) and medium doses (-26 percent). However, the dose of 100 mg / kg induced a significant increase (114 percent) in plasma total cholesterol on day 20 of gestation compared to controls. NiCl2 s.c. induced a significant increase in plasma glucose (+125 percent) on day 20 of pregnancy. The pretreatment with Se counteracted the effects of NiCl2 on plasma glucose, total cholesterol and triglycerides. NiCl2 administered in the drinking water induced a significant increase (<0.05) in plasma triglycerides (+68 percent) and cholesterol (+49 percent) on day 20 of gestation, while on day five of gestation NiCl2 s.c. induced a significant decrease in cholesterol (-31 percent) compared to controls. All doses of NiCl2 induced an alteration of liver architecture. Co-administration of Se with NiCl2 restored the structure of the liver. These results suggested that selenium has a hepatoprotective role against the toxicity induced by NiCl2 administered subcutaneously in preimplanted rats.

Effects of nickel chloride on reproduction, biochemical parameters in wistar albino rats and possible antagonistic role of selenium - Mouffouk, Samia; Ounassa Adjroud (WASET 2011 : World Academy of Science, Engineering and Technology, January 25-27, 2011)

Protective Effects of Selenium against Nickel Chloride-Induced Neprotoxicity in Preimplanted Rats - Ounassa Adjroud (e 6th Annual International Symposium on Environment, 16-19 May, 2011)
The environmental exposure to nickel may have a disastrous impact on human and animal public health. In this study we evaluated the protective effects of selenium against the nephrotoxic effects of NiCl2 in the preimplanted rats. NiCl2 was given on day 3 of pregnancy either as a single subcutaneous (sc) dose of 25, 50 or 100 mg/kg or in distilled drinking water at a dose of 20 mg/L/day for 16 consecutive days. Selenium was given as a sc injection (0.3 mg/kg) together with the higher dose (100 mg/kg) of NiCl2. Changes in plasma creatinine and urea were measured in treated and control groups on days 5 and 20 of gestation. The results showed that 100 mg / kg NiCl2 sc induced a significant increase in plasma creatinine on day 5 of gestation compared with controls. In contrast, on day 20 of gestation the NiCl2 induced a significant decrease in creatinine induced by doses of 25 and 50 mg / kg, whereas dose of 100 mg / kg increased plasma creatinine. Coadministration of selenium with NiCl2 significantly improved plasma creatinine on 5 and 20 days of gestation compared with NiCl2 administered alone. Moreover, on day 5 of gestation the NiCl2 increased significantly plasma concentrations of urea with the low and medium doses which became very significant with the highest dose. On day 20 of gestation, 50 mg / kg NiCl2 induced a significant decrease in plasma urea while the dose of 100 mg / kg induced an increase. Coadministration of selenium did not improve the concentrations of urea induced by NiCl2 alone. The NiCl2 administered in drinking water had no effect on plasma creatinine and urea. 3 doses of NiCl2 (sc) induced an alteration of renal architecture which is markedly improved by Selenium. The NiCl2 taken orally affects the medulla. These results suggested that selenium had no effect against nephrotoxicity induced by NiCl2 administered subcutaneously in pregnant rats.

Copper(II) bromide as efficient catalyst for silyl- to bisarylmethyl ethers interconversion (transprotection) - Specklin, Simon; Gallier, Florian; RofiaMezaache; Hassina Harkat; Yénimégué Albert Dembelé; Jean-Marc Weibel; Aurélien Blanc; Patrick Pale (Tetrahedron Letters, 2011)
Primary and secondary silylated alcohols are easily converted to bis(methoxyphenyl)methyl (BMPM) ethers in good yields using CuBr2 as catalyst in acetonitrile at room temperature. Various other protecting groups are compatible with this mild and convenient process. Graphical abstract Primary and secondary silylated alcohols are easily and rapidly converted to bis(methoxyphenyl)methyl (BMPM) ethers in good yields using CuBr2 as catalyst in acetonitrile at room temperature. Various other protecting groups are compatible with this mild and convenient process. <figure id="f0025"> </figure>
Keywords: Alcohol; Bis(methoxyphenyl)methyl; Copper; Protecting group; Silyl; Transprotection

Copper(II) Bromide as Efficient Catalyst for Silyl- to Bisarylmethyl Ethers Interconversion (Transprotection) - Specklin, Simon; Gallier, Florian; Mezaache, Roufia; Hassina Harkat; Yénimégué, Albert; Jean-Marc Weibel; Aurélien Blanc; Patrick Pale (Tetrahedron Letters, 2011)
Primary and secondary silylated alcohols are easily converted to bis(methoxyphenyl)methyl (BMPM) ethers in good yields using CuBr2 as catalyst in acetonitrile at room temperature. Various other protecting groups are compatible with this mild and convenient process. Graphical abstract Primary and secondary silylated alcohols are easily and rapidly converted to bis(methoxyphenyl)methyl (BMPM) ethers in good yields using CuBr2 as catalyst in acetonitrile at room temperature. Various other protecting groups are compatible with this mild and convenient process. <figure id="f0025"> </figure>

Registre du cancer de la wilaya de Batna, bulletin de l’année 2011 - Mohamed-Larbi Bouhidel; Fayçal Beichi; Atika Bouhidel; Hachani Khadraoui; Imene Benamira; Mahdia Saidi; Abdelouahab Maaref; Hocine Bounecer (Batna Journal of Medecine Sciences, 2011)
Cancer register in the Wilaya of Batna is a population based register that covers 1,173,852 inhabitants in 2011 (estimation made with a rate of population increase of 1.58% beginning from the 2008 RGPH census). A total number of 768 new cases has been identified, which represents a standardized incidence of 78.2 cases per 100,000. The most prevalent cancers in males were lung cancer (12.2 cases / 100,000 inhabitants), colorectal cancers and bladder cancers, respectively. In females, breast cancer was largely the most prevakent type, representing 30% of the total cancers, followed by colorectal cancers and thyroid cancer. In children aged 0 to 14, the standardized prevalence was 1.9 per 100,000 inhabitants, largely dominated by malignant blood and lymphoid organs cancers.

Rôle antagoniste du Sélénium des effets hépatotoxiques induits par le Nicl2 chez la rate Wistar préimplantée - Ounassa Adjroud (3e congrès de toxicologie.11-13 Novembre, 2010)

Protective effects of selenium against potassium dichromate-induced hematotoxicity in female and male Wistar albino rats - Ounassa Adjroud (Annales de Toxicologie Analytique, 2010)
Objective: Potassium dichromate (K2Cr2O7) is a potent pollutant for human and animal health. The purpose of the current work is to compare the effect of K2Cr2O7 using variations in the dose, route of administration and duration of exposure in male and female Wistar albino rats and to research the interaction of chromium and selenium with a special focus on hematopoiesis.  Materials and methods: K2Cr2O7 was subcutaneously administered alone (10, 50 and 100 mg/kg body weight) or K2Cr2O7 (10 mg/kg) in association with selenium (0.3 mg/kg) was administered to female Wistar albino rats. Male rats received in their drinking water K2Cr2O7 (30 mg/L/day) alone or in association with Se (0.3 mg/L/day) for 20 consecutive days. The hematological parameters were evaluated on days 3, 6 and 21 after subcutaneous (sc.) treatment in female rats and on days 10 and 20 after oral administration in male rats.  Results: K2Cr2O7− induced during the first three days a significant (p < 0.05) dose-dependent decrease in the number of erythrocytes, platelets, leucocytes, lymphocytes and the hematocrit levels, and a dose-dependent increase in the number of granulocytes and monocytes. In the drinking water, chromium sc. significantly decreased the number of leucocytes and lymphocytes on day 10 after treatment and elevated the number of granulocytes and monocytes 20 days later. Selenium sc. counterbalanced the hematotoxic effects of chromium in female rats.  Conclusion: These results suggest that the selenium has a protective role against the hematotoxicity of subcutaneous chromium in female Wistar rats.

Iridoids and flavonoid from Linaria aegyptiaca (L.) Dum. subsp. fruticosa - Maria Ferhat; Hassina Harkat; Catherine Lavaud; Hamada Haba; Christophe Long; Mohammed Benkhaled (Biochemical Systematics and Ecology, 2010)
Keywords: Flavonoid; Iridoids; Scrophulariaceae

Effet toxique du chlorure de Nickel sur les paramètres de développement chez la rate gestante de souche Wistar - Ounassa Adjroud; Mouffouk, Samia (2èmes Journées Nationales sur l’Environnement & les Conditions de Travail. 27 Avril 2009 Université El Hadj Lakhdar, 2009)

Effects of potassium dichromate on haematological. parameters in female and male Wistar albino RATS - Ounassa Adjroud (Ass. Univ. Bull. Environ. Res, 2009)
Hexavalent chromium is a potent toxic agent. It has been found to be carcinogenic in human and animal. The purpose of the current work is to compare the effect of potassium dichromate (K2Cr2O7) using variations in the dose, route of administration, and duration of exposure in male and female wistar albino rats with special focus on hematological parameters. K2Cr2O7 was administered either in the drinking water with a dose of 30 mg/l for 20 consecutive days to male wistar albino rats, or as a single dose subcutaneously (s.c) at 10, 50 and 100 mg/Kg body weight (b w) to female wistar albino rats. Control groups received NaCl 0.9% (0.3 ml s.c), or drinking distilled water. Haematological parameters were recorded on day 3, 6, and 21 after subcutaneous exposure, or on day 10 and 20 after oral treatment. 10 mg/Kg b w of K2Cr2O7 given subcutaneously induced during the first three days a marked decrease in the number of erythrocytes (-6%) of leucocytes (-30%) of platelets (-48%) and of hematocrit values (-15%), while the number of granulocytes is augmented (+124%) in comparison with control. Hemoglobin concentration and lymphocyte counts decreased markedly on day 6 after exposure. Chromium 50 mg/Kg b w, s.c mainly affected during the first three days the leucopoietic indices inducing leucopoenia (-55%), lymphopoenia (-57%), monocytosis (+104%), granulocytosis (+204%), and thrombocytosis (+38%) if compared with control, while the erythrocytic counts and hemoglobin concentration decreased from day 6 (-22%) and (-21%) respectively until day 21 (-41%) and (-36%) respectively, and hematocrit values decreased at the end of experiment (-36%) in comparison with control. The higher dose of chromium (100 mg/Kg b w, s.c) reduced during the first three days the number of erythrocytes (-20%), platelets (-20%), total leucocytes (-55%), lymphocytes (-59%) and augmented the number of monocytes (+56 %), and granulocytes (+166%), while on day 6 the number of platelets augmented (+27%) in comparison with control. In drinking water, 30 mg/l of chromium given to male wistar albino rats had no effect on all erythropoietic parameters studied with the exception of the elevation (+21%) in platelet counts at the end of exposure, while the number of lymphocytes and total leucocytes were significantly reduced on day 20 after exposure (-37%) and (-37%) respectively. Conversely, the number of granulocytes and monocytes markedly increased on day 10 after exposure (+42%) and (+22%) respectively if compared with control. Short-term exposures to low dose of K2Cr2O7, s.c induce in female wistar albino rats erythrocytopenia, thrombocytopenia, leucopoenia, lymphopaenia, granulocytosis, monocytosis, and a decrease in hematocrit values and hemoglobin concentration while in drinking water chromium was susceptible to affect in male rats the immune response inducing leucopoenia, lymphopoenia, monocytosis, and granulocytosis, while this oral route of exposure had no effect on erythropoietic parameters.

EFFECTS OF NICKEL CHLORIDE ON HEMATOLOGICAL AND DEVELOPMENTAL PARAMETERS IN Wistar albino PREGNANT RATS - Ounassa Adjroud; MOUFFOK, S (Ass. Univ. Bull. Environ. Res, 2009)
Several reports have suggested that soluble salts nickel may affect on hematopoiesis and development. In this study female Wistar albino rats (180-300g) received NiCl2, 6H2 O, subcutaneously (25, 50 and 100 mg/kg body weight (b w) or in drinking water (20 mg/100 ml). Selenium (0.3 mg/kg b w, s.c.) was combined to NiCl2 (100 mg/kg b w, s.c.). Control groups received NaCl 0.9% (0.3 ml s.c) or drinking distilled water. All groups of rats were injected on day 4 of pregnancy in pre-implantation period. Haematological parameters were recorded on day 6 and 21 of pregnancy. Developmental parameters were assessed on day 21 of pregnancy. 25 mg/kg b w, of NiCl2 s.c, induced on day 6 an immediate and significant decrease in erythrocyte counts, hematocrit values, and haemoglobin concentrations. This depletion was maintained on day 21 of pregnancy compared to control values.On other hand 50 mg/k b w, NiCl2, s.c, reduced on day 6 of pregnancy the erythrocyte counts, hematocrit values and platelets counts. Inversely, on day 21 this dose elevated the erythrocyte counts, hematocrit values and haemoglobin concentrations ,with depletion of the platelets counts compared to control values. In group introduced 100 mg/kg b w, of NiCl2, s.c had no effect on all haematological parameters studied. NiCl2, significantly reduced the maternal body weight on day 6 and 21 of pregnancy in a dose – dependent manner in rats treated subcutaneously and in drinking water compared with control values. NiCl2, s.c. (100 mg/kg b w) markedly reduced the number of live fetuses and elevated the number of abortions on day 21 of pregnancy compared to control values. NiCl2, s.c or in drinking water had no effect on fetal body weight. Selenium (0.3 mg/kg b w, s.c.) combined to NiCl2 (100 mg/kg b w, s.c.) did not improve the effect of NiCl2.

Effets du k2cr2o7 administré à différentes doses et voies d’administration sur l’érythropoïèse chez les rats males et femelles de la souche Wistar - Ounassa Adjroud (1e Séminaire International sur la Valorisation des Ressources Naturelles des Zones semi - Arides , 3- 4 Novembre, 2008)

Effets du k2cr2o7 administre à différentes doses et voies d’administration sur la leucopoïèse chez les rats males et femelles de la souche wistar - Ounassa Adjroud (2èmes Journées Internationales de Toxicologie. Société Algérienne de Toxicologie. 03 - 04 Décembre, 2008)

Effet toxique du chlorure de Nickel sur la leucopoïèse et les paramètres de développement chez la rate gestante de souche Wistar - Ounassa Adjroud; Mouffouk, Samia (2èmes Journées Internationales de Toxicologie. Société Algérienne de Toxicologie. 03 - 04 Décembre, 2008)

Effet de l'acétate de plomb sur les paramètres hématologiques, la glycémie et le poids chez les rats wistar mâles et femelles - Mouffouk, Samia; Ounassa Adjroud; BENSMINA (2ème Journées Nationales sur la biodiversité et l'environnement naturel et la qualité de vie dans la région des Aurès. 27-29 mai 2007 Université El Hadj Lakhdar BATNA, 2007)

Effets des différentes doses et des différentes voies d'administrations de l'acétate de Plombs sur les paramètres hématologiques, les concentrations plasmatiques en Glucose et le poids chez les rats Wistar mâles et fe - Ounassa Adjroud; Mouffouk, Samia (The Fourth Scientific Conferences on the Environment & Natural. 14-16 May, 2007)

Effets des différentes doses et des différentes voies d'administrations de CdCl2 s sur les paramètres hématologiques, les concentrations plasmatiques en Glucose et le poids chez les rats Wistar mâles et femelles - Ounassa Adjroud; Mouffouk, Samia (The Fourth Scientific Conferences on the Environment & Natural. 14-16 May, 2007)

Interaction des enképhalines avec l’Œstradiol 17beta et la progestérone placentaires et utérines chez la rate pré parturiente - Ounassa Adjroud (2e Colloque Euroméditerranéen de Biologie Environnementale , 07 -10 Décembre, 2006)

Interaction des enképhalines avec l’Œstradiol 17beta et la progestérone placentaires et utérines chez la rate pré parturiente - Ounassa Adjroud; Clabaut ,M (2e Colloque Euroméditerranéen de Biologie Environnementale , 07 -10 Décembre, 2006)

Interaction des enképhalines avec les prostaglandines F2 alpha et E2 placentaires et utérines chez la rate pré parturiente - Ounassa Adjroud (2e Colloque Euroméditerranéen de Biologie Environnementale 07 -10 Décembre, 2006)

Effets des inhibiteurs de l’enképhalinase sur les stéroïdes sexuels : la progestérone et l’oestradiol chez la rate préparturiente - 1er Séminaire International de Biologie et Physiologie de la Reproduction, 6-7 Décembre (2005)

Interaction de la TSH , T3 et T4 avec les gonadotrophines FSH et LH chez la femme pré- ménopausée - Ounassa Adjroud; Allaoui, N; Benour, T (1er Séminaire International de Biologie et Physiologie de la Reproduction, 6-7 Décembre, 2005)

La douleur et la morphinothérapie - Ounassa Adjroud (Journées de concertation pour la finalisation du programme national de Recherche en Santé. 26-27 Février, 1997)

Les opiacés endogènes et la motricité utérine pendant la gestation - Ounassa Adjroud (Journal Algérien de Médecine, 1997)

Action Of Naloxone And Acetorphan, On Uterine Contractions Induced By Oxytocin -in Periparturient Rat In Vivo - Ounassa Adjroud (Synthèse, 1997)
Theffects' in vivo of acetorphan, an _enkephalinase inhibitor and naloxone, an opiate antagonist on the - - oxytocin- induced myometrial mechanical activity were studied at day 21 of pregnancy in rats. Acetarpban" I 10 mg kg -1 (i.v.) increased (344%) spontaneous uterine contractions duration only at 0-10 min period, but - did not modify amplitude. This increase in the duration was blocked by naloxone 5 mg ks -1, which had no effect on the amplitude or duration of contractions when given alone. Oxytocin (~T), I, 10 and I 100 mIU (i.v.) stimulated in a dose dependent manner, spontaneous uterine contractions duration but did not alter the amplitude of contractions. Blocking the opioid peptides by naloxone, 5 mg kg -1 (s.c.) injected --10min before OT strongly potentiated the effect of the lowest dose of OT (1 mlU) b-yabout of 59&Ofn and doubled the amplitude of contractions during the 30 min observation period. When acetorphan, 10 mg kg _-1 (i.v.) administered 30 min before the lowest dose of OT studied, 1 mID (i.v.), It induced a slight increase by .about 88% in uterine contractions duration produced by OT alone, The amplitude remained unchanged. These -results suggested that uterine contractions induced by OT in late pregnancy in rats might be regulated by enkephalinergie and enkephalinasic systems

Peripheral excitatory effects of two enkephalinase inhibitors, acetorphan and thiorphan, and an enkephalin analogue, [d-Ala2–Met5]-enkephalinamide, on uterine motility in periparturient rats in vivo and in vitro - Ounassa Adjroud (Journal for Reproduction and Fertility, 1995)
The effects of two enkephalinase inhibitors, acetorphan and thiorphan, and the enkephalin analogue [d-Ala2\p=n-\Met5]-enkephalinamide (DAMEA), on spontaneous uterine contractions were studied at day 21 of pregnancy in rats following treatment in vivo or in vitro. Acetorphan (10 mg kg\m=-\1)and thiorphan (1 mg kg\m=-\1),immediately after their i.v. administration, increased the duration of spontaneous contractions 3.4- and 4.6-fold, respectively, but did not modify the maximum amplitude. Similarly, thiorphan (40 \g=m\moll\m=-\1) increased the duration of contractions when administered in vitro. Thiorphan was ineffective during the first 30 min when given into the cerebral ventricles (50 \g=m\gper rat). These results suggest that the enkephalinase inhibitors are acting via a peripheral opioid pathway; and this conclusion is supported by the observation that thiorphan potentiated the stimulatory effect of a submaximal dose of DAMEA administered in vitro. The excitatory effects of DAMEA and the enkephalinase inhibitors were blocked by naloxone. This antagonistic effect of naloxone on uterine motility in the periparturient rat uterus, induced by either acetorphan and thiorphan or DAMEA, seems to be regulated by peripheral opiate receptors. Naloxone (10 mg kg\m=-\1 s.c.) increased both the amplitude and duration of uterine motility in vivo; however, naloxone (26 \g=m\moll\m=-\1 and 52 \g=m\moll\m=-\1) produced a paradoxical dose-dependent biphasic effect in vitro.

Effets stimulateurs de deux inhibiteurs de l’enkephalinase sur la motilité utérine chez la rate préparturiente - Ounassa Adjroud (Journée Scientifique Vétérinaire. 22 Mai 1989, El Hadj Lakhdar, 1989)

Variation of myometrial activities and steroid sexual hormones following bilateral ovariectomy in the rat at midpregnancy - Clabaut ,M; Duclos, R; Chartrel, N; Ounassa Adjroud; Acritopoulou-Fourcroy, S; Collado, H; Schrub, J C (Acta Physiol Hung, 1988)
The effects of bilateral ovariectomy on uterine motility and levels of progesterone, oestradiol, cAMP, adrenaline and PGF2 alpha were studied in the rat at midpregnancy. Animals were randomly divided into two groups, at least 15 rats in each, sham-operated serving as controls and ovariectomized. The spontaneous uterine mechanical activity of Wistar rats was recorded isometrically and the electrical activities were recorded simultaneously by two bipolar electrodes. Within 30 minutes of ovariectomy a significant increase of the amplitude of uterine contractions was observed and the simultaneity of electrical activity was significantly improved; these effects became more pronounced at 1h post-ovariectomy (p less than 0.005). Plasma progesterone levels decreased by 20% (p less than 0.01) at 30 min and by 50% (p less than 0.001) 1h after ovariectomy, whereas oestrogen levels remained unchanged. Levels of adrenaline, cAMP and PGF2 alpha in the uterine tissue 1h following ovariectomy were affected as follows: adrenaline (p less than 0.05) and cAMP (p less than 0.001) were reduced and PGF2 alpha augmented (p less than 0.05). It appears that variation of the ratio oestrogens/progesterone induces precociously the activation of uterine mobility and exerts an effect on some factors involved in the regulation of the rat myometrium at midpregnancy.